Fiber-reinforced thermoplastic resin composition and resin-metal composite
By using a fiber-reinforced thermoplastic resin composition, combined with a specific styrene-based polymer and a rubber-like elastomer, the problem of insufficient heat resistance and dimensional stability of the resin member in the reflow soldering process is solved, and a resin material with high performance and durability is achieved.
Patent Information
- Application Number
- CN202380056197.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-26
- Filing Date
- 2023-07-21
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to provide sufficient heat resistance and dimensional stability in the reflow soldering process, resulting in the deformation of the resin member at high temperatures and affecting performance.
A fiber-reinforced thermoplastic resin composition containing a thermoplastic resin composition and glass fibers having a flat cross-section is used to form a reflow-resistant resin material in combination with a specific styrene-based polymer, a rubber-like elastomer and a crystallization nucleating agent.
Excellent heat resistance and dimensional stability at high temperatures are achieved, and the performance and durability of the resin material in the reflow soldering process are improved.
Smart Images

Figure CN119522250A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a fiber-reinforced thermoplastic resin composition and a reflow-resistant resin material comprising the same, and more particularly to a syndiotactic polystyrene resin composition and a reflow-resistant resin material comprising the same.
[0002] The present invention also relates to a resin-metal composite, and more specifically, to a resin-metal composite comprising a syndiotactic polystyrene resin composition and a metal member. Background Art
[0003] In the past, as a method for mounting electronic components and electrical components on substrates, the reflow method was used. The reflow method is a method in which electronic components are temporarily fixed on a member on which solder paste is pre-applied at a predetermined position, and then the member is heated by infrared rays, hot air, etc. to melt the solder to fix the electronic components. The reflow method can increase the mounting density of electronic components on the surface of the substrate.
[0004] In recent years, with the development of surface mounting technology in the field of electronic equipment and automotive electrical components, the reflow soldering method with excellent mounting density is becoming popular. In addition, due to the recent increase in environmental awareness, lead-free reflow soldering has become the mainstream, but due to the rising price of silver, low-silver lead-free solder that reduces the amount of silver added to lower the melting point of lead-free solder has attracted much attention. Here, for the resin used in substrates, connectors, housings, etc. for fixing electronic components, heat resistance that can withstand the low-silver lead-free reflow soldering process is required.
[0005] Practically, heat-resistant resins that can cope with low-silver lead-free reflow soldering processes include liquid crystal polymers, polyphenylene sulfide, and aromatic polyamides. However, due to their large specific gravity and poor dimensional stability due to water absorption, they are not necessarily suitable for use in electronic equipment and automotive electrical components.
[0006] It is known that styrene polymers having a syndiotactic structure have excellent mechanical strength, heat resistance, electrical properties, water absorption dimensional stability, chemical resistance, etc., and are expected to have a variety of uses. Among them, styrene polymers having a syndiotactic structure are effectively utilized for excellent chemical resistance, heat resistance, electrical properties and water absorption dimensional stability, and are attracting attention in electronic devices, vehicle-mounted / electrical components, transformer / coil power modules, relays, sensors, etc.
[0007] For example, Patent Document 1 discloses a thermoplastic resin composition mainly comprising a styrene polymer having a syndiotactic structure, various polymers, a thermoplastic resin and / or a rubbery elastomer, a fiber reinforcement, and an organic filler or an inorganic filler.
[0008] In addition, comparative document 2 discloses a styrene resin having a syndiotactic structure, wherein, when the total endothermic amount measured by differential scanning calorimetry at a heating rate of 20°C / min is set to 100%, the proportion of the endothermic amount obtained in the range of 175 to 260°C is less than 30%.
[0009] In addition, technologies for integrating metal and resin, which are dissimilar materials, have been developed, mainly in the fields of electronics / electromechanical, automobiles, and household appliances. Products in the above-mentioned fields are often used in harsh environments such as alternating exposure to high and low temperatures, depending on the use conditions and use environment. Therefore, materials used in the above-mentioned fields are required to have durability, so-called heat shock resistance, that does not cause damage such as cracking even when alternately exposed to high and low temperatures.
[0010] For example, Reference 3 discloses an insert molded product having an insert member such as metal and a resin composition containing a polyarylene sulfide resin, an inorganic filler, and an olefin copolymer.
[0011] Patent Document 4 discloses an insert molded product including an insert member such as a metal and a resin composition containing a polyarylene sulfide resin, a fibrous inorganic filler, a non-fibrous inorganic filler, and an olefin copolymer.
[0012] Patent Document 5 discloses an insert-molded product obtained by insert-molding a resin composition containing a polyarylene sulfide resin, a fibrous reinforcing agent having a flat cross-sectional shape, and a thermoplastic elastomer with a metal or the like.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Publication No. 2004-155928
[0016] Patent Document 2: International Publication No. 2019 / 107526
[0017] Patent Document 3: International Publication No. 2019 / 208706
[0018] Patent Document 4: Japanese Patent Application Publication No. 2020-109135
[0019] Patent Document 5: Japanese Patent Application Publication No. 2005-161693 Summary of the invention
[0020] Problems to be solved by the invention
[0021] Patent Document 1 discloses a thermoplastic resin composition containing a specific styrene polymer having a syndiotactic structure and having excellent mechanical strength. However, in the reflow soldering process, resin components constituting substrates, connectors, etc. are exposed to high temperatures, so when the thermoplastic resin composition of Patent Document 1 is used for resin components, it cannot be said that the "reflow soldering resistance" is sufficient.
[0022] In addition, Patent Document 2 discloses a styrene polymer having a syndiotactic structure and having a specific ratio of endothermic heat calculated under specific conditions. However, in the reflow soldering process, the resin component is exposed to high temperature, which easily causes deformation of the resin component and sometimes fails to exert full performance. Therefore, when only the styrene resin having a syndiotactic structure of Patent Document 2 having specific thermal properties is used, it cannot be said that the practicality is sufficient in the reflow soldering process. In addition, Patent Document 2 also discloses specific resin compositions, but these compositions cannot be said to be sufficient as resin components used in the surface mount technology (SMT: Surface mount technology) in the field of electronic equipment and automotive electrical components in recent years, especially from the perspective of heat resistance.
[0023] An object of the first subject of the present invention is to provide a fiber-reinforced thermoplastic resin composition having excellent heat resistance and dimensional stability at high temperatures, and a reflow-resistant resin material including the resin composition.
[0024] In addition, Patent Document 3 discloses that by using three types of inorganic fillers in the form of plates, fibers, and granules in combination with an olefin copolymer in a polyarylene sulfide-based resin, even when the welded portion (counterflow welded portion) of the resin member is formed so as to coincide with the stress concentration portion, both thermal shock resistance and low warpage can be achieved. However, in Patent Document 3, the study based on the difference in expansion coefficient between the metal member and the resin member in the insert molded product and the study of the physical properties of the parallel flow welded portion are insufficient, and in particular, the thermal shock resistance of the parallel flow welded portion cannot be said to be sufficient.
[0025] Patent Document 4 discloses that, as an inorganic filler to be blended in a polyarylene sulfide resin, a resin composition in which a fibrous inorganic filler having a predetermined diameter ratio and a non-fibrous inorganic filler are combined and blended in a predetermined ratio is used, thereby enabling the insert molded product to have excellent heat shock resistance. In addition, Patent Document 5 discloses that, by using a resin composition having a polyarylene sulfide resin as a main body and blending a flat fibrous reinforcing agent having a specific cross-sectional shape and a thermoplastic elastomer therein, the heat shock resistance can be improved without significantly reducing the mechanical properties. However, in Patent Documents 4 and 5, the research based on the difference in expansion coefficient between the metal component and the resin component in the insert molded product is insufficient, and in addition, the physical properties of the welded portion have not been studied, and it cannot be said that the heat shock resistance of the welded portion is sufficient.
[0026] A second object of the present invention is to provide a resin-metal composite having excellent thermal shock resistance.
[0027] Means for solving problems
[0028] The present inventors have conducted intensive research and found that the first problem can be solved by using a fiber-reinforced thermoplastic resin composition comprising a thermoplastic resin composition and glass fibers having a flat cross-section, wherein the thermoplastic resin composition comprises a specific styrene polymer having a syndiotactic structure, a rubbery elastomer, and a crystal nucleating agent. That is, the first aspect of the present invention relates to the following [1] to
[13] .
[0029] [1] A fiber-reinforced thermoplastic resin composition comprising a thermoplastic resin composition (T) and glass fibers (G) having a flat cross section, wherein the thermoplastic resin composition (T) comprises 100 parts by mass of a styrene-based resin composition (S) and 0.6 to 2.0 parts by mass of a crystal nucleating agent (C), wherein the styrene-based resin composition (S) comprises 83 to 100 parts by mass of a styrene-based polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 0 to 17 parts by mass of a rubbery elastomer (B), and the content of the glass fibers (G) is 33.0 to 65.0% by mass relative to the total of the thermoplastic resin composition (T) and the glass fibers (G).
[0030] [2] The fiber-reinforced thermoplastic resin composition according to [1], further comprising 0.1 to 5.0 parts by mass of a modified polyphenylene ether (D) based on 100 parts by mass of the styrene-based resin composition (S).
[0031] [3] The fiber-reinforced thermoplastic resin composition according to [1] or [2], wherein the weight average molecular weight of the styrene-based polymer (A) is less than 200,000.
[0032] [4] The fiber-reinforced thermoplastic resin composition according to any one of [1] to [3], wherein the profile ratio of the glass fiber (G) is 3.5 to 4.5.
[0033] [5] The fiber-reinforced thermoplastic resin composition according to any one of [1] to [4], wherein the glass fiber (G) has a fiber diameter of 10 μm or more.
[0034] [6] The fiber-reinforced thermoplastic resin composition according to any one of [1] to [5], wherein the reflow shrinkage of TD measured by treating a test piece formed from the fiber-reinforced thermoplastic resin composition in accordance with IEC60068-2-58 is 0.20% or less, and the anisotropy of the reflow shrinkage (TD / MD) is 4.5 or less.
[0035] [7] The fiber-reinforced thermoplastic resin composition according to any one of [1] to [6], wherein a test piece formed from the fiber-reinforced thermoplastic resin composition has a deflection temperature under load measured in accordance with method A of ISO 75-1,2 (2020) of 255°C or higher.
[0036] [8] A reflow-resistant resin material comprising the fiber-reinforced thermoplastic resin composition according to any one of [1] to [7].
[0037] [9] A molded body for reflow soldering, comprising the reflow soldering resistant resin material described in [8].
[0038]
[10] A resin-metal composite comprising the molded body for reflow soldering described in [9] and a metal member.
[0039]
[11] A connector formed from the resin-metal composite described in
[10] .
[0040]
[12] The connector according to
[11] is used in a reflow soldering process.
[0041]
[13] A connector according to
[11] , which is used in a reflow soldering process based on surface mounting.
[0042] In addition, the present inventors have conducted intensive research and found that the second problem is solved by using a resin-metal composite comprising a resin member formed of a reinforced thermoplastic resin composition and a metal member, wherein the difference between the linear expansion coefficient of the resin member in TD and the linear expansion coefficient of the metal member is within a certain range, and the bending fracture strain of a parallel flow welded test piece formed of the reinforced thermoplastic resin composition is greater than or equal to a specific value. That is, the second aspect of the present invention relates to the following
[14] to
[25] .
[0043]
[14] A resin-metal composite comprising:
[0044] A resin member formed of a reinforced thermoplastic resin composition containing a thermoplastic resin composition (T2) and a glass filler (G2); and
[0045] Metal components,
[0046] The coefficient of linear expansion (CTE) of the TD of the resin member TD ) and the linear expansion coefficient (CTE) of the above metal components M ) (CTE TD -CTE M ) is 6.0×10 -5 / ℃ below,
[0047] The bending fracture strain of the parallel flow welded test piece formed of the reinforced thermoplastic resin composition is 1.15% or more.
[0048]
[15] The resin-metal composite according to
[14] , wherein the thermoplastic resin composition (T2) comprises a styrene-based resin composition (S2), wherein the styrene-based resin composition (S2) is composed of 75 to 94 parts by mass of a styrene-based polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 6 to 25 parts by mass of a rubbery elastomer (B).
[0049]
[16] The resin-metal composite according to
[14] or
[15] , wherein the glass filler (G2) is one or more selected from glass fibers and glass flakes having a flat cross-section.
[0050]
[17] The resin-metal composite according to
[16] , wherein the profile ratio of the glass fiber having a flat cross section is 3.5 to 4.5.
[0051]
[18] The resin-metal composite according to
[16] or
[17] , wherein the glass fiber having a flat cross-section has a fiber diameter of 10 μm or more.
[0052]
[19] The resin-metal composite according to any one of
[16] to
[18] , wherein the glass flakes are flaky particles.
[0053]
[20] The resin-metal composite according to any one of
[14] to
[19] , wherein the content of the glass filler (G2) is 20.0 to 65.0% by mass relative to the total of the thermoplastic resin composition (T2) and the glass filler (G2).
[0054]
[21] The resin-metal composite according to any one of
[15] to
[20] , wherein the thermoplastic resin composition (T2) further comprises 0.6 to 2.0 parts by mass of a crystal nucleating agent (C) based on 100 parts by mass of the styrene resin composition (S2).
[0055]
[22] The resin-metal composite according to any one of
[15] to
[21] , wherein the thermoplastic resin composition (T2) further comprises 0.1 to 15.0 parts by mass of a modified polyphenylene ether (D) relative to 100 parts by mass of the styrene resin composition (S2).
[0056]
[23] The resin-metal composite according to any one of
[15] to
[22] , wherein the thermoplastic resin composition (T2) further comprises 0.05 to 3.0 parts by mass of a release agent (F) relative to 100 parts by mass of the styrene resin composition (S2).
[0057]
[24] The resin-metal composite according to any one of
[15] to
[23] , wherein the weight average molecular weight of the styrene-based polymer (A) is less than 200,000.
[0058]
[25] The resin-metal composite according to any one of
[14] to
[24] , wherein the metal component is at least one selected from aluminum, stainless steel, copper, titanium and alloys thereof.
[0059] Effects of the Invention
[0060] According to the first aspect of the present invention, a fiber-reinforced thermoplastic resin composition having excellent heat resistance and dimensional stability at high temperatures, and a reflow-resistant resin material containing the resin composition can be obtained.
[0061] According to the second aspect of the present invention, a resin-metal composite having excellent thermal shock resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram showing a cutout portion of a test piece for measuring the bending fracture strain of a parallel flow welded test piece formed of a reinforced thermoplastic resin composition in the second embodiment of the present invention.
[0063] Figure 2 This is a schematic cross-sectional view of a mold for a parallel flow welding test piece formed of a reinforced thermoplastic resin composition in the second embodiment of the present invention.
[0064] Figure 3 This is a schematic plan view of a cavity portion of a mold for a parallel flow welding test piece formed of a reinforced thermoplastic resin composition in the second aspect of the present invention, as viewed from the upper side of the mold.
[0065] Figure 4 is a coefficient of linear expansion (CTE) for measuring the TD of the resin member in the second embodiment of the present invention. TD ) is a schematic diagram of a cutout portion of a test piece.
[0066] Figure 5 This is a schematic diagram of a test piece for evaluating the thermal shock resistance of the resin-metal composite according to the second embodiment of the present invention.
[0067] Figure 6 This is a schematic cross-sectional view of a test piece for evaluating the thermal shock resistance of the resin-metal composite according to the second embodiment of the present invention.
[0068] Figure 7 This is a schematic diagram of a mold of a test piece for evaluating the thermal shock resistance of the resin-metal composite according to the second aspect of the present invention. DETAILED DESCRIPTION
[0069] [Fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention]
[0070] A fiber-reinforced thermoplastic resin composition according to a first embodiment of the present invention comprises a thermoplastic resin composition (T) and glass fibers (G) having a flat cross section, wherein the thermoplastic resin composition (T) comprises 100 parts by mass of a styrene-based resin composition (S) and 0.6 to 2.0 parts by mass of a crystal nucleating agent (C), wherein the styrene-based resin composition (S) comprises 83 to 100 parts by mass of a styrene-based polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 0 to 17 parts by mass of a rubber-like elastomer (B), and the content of the glass fibers (G) is 33.0 to 65.0% by mass relative to the total of the thermoplastic resin composition (T) and the glass fibers (G).
[0071] Hereinafter, each item will be described in detail.
[0072] <Thermoplastic resin composition (T)>
[0073] The thermoplastic resin composition (T) comprises 100 parts by mass of a styrene-based resin composition (S) and 0.6 to 2.0 parts by mass of a crystal nucleating agent (C), wherein the styrene-based resin composition (S) is composed of 83 to 100 parts by mass of a styrene-based polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 0 to 17 parts by mass of a rubbery elastomer (B).
[0074] <Styrene resin composition (S)>
[0075] The styrene resin composition (S) comprises 83 to 100 parts by mass of a styrene polymer (A) having a syndiotactic structure and 0 to 17 parts by mass of a rubbery elastic body (B).
[0076] <Styrene polymer having a syndiotactic structure (A)>
[0077] The styrene polymer (A) having a syndiotactic structure (hereinafter also referred to as SPS (A)) is a styrene resin having a high degree of syndiotactic structure. In this specification, "syndiotactic" means that the proportion of the alternating arrangement of benzene rings in adjacent styrene units relative to the plane formed by the main chain of the polymer block (hereinafter referred to as syndiotacticity) is high.
[0078] Stereotacticity can be determined by carbon isotope-based nuclear magnetic resonance (NMR) 13 C-NMR method) for quantitative identification. 13 The C-NMR method can quantitatively determine the existence ratio of a plurality of consecutive structural units, for example, two consecutive monomer units as a dyad, three monomer units as a triad, and five monomer units as a pentad.
[0079] In the first embodiment of the present invention, the "styrene resin having a high degree of syndiotactic structure" refers to a styrene polymer such as polystyrene, poly(hydrocarbon-substituted styrene), poly(halogenated styrene), poly(halogenated alkyl styrene), poly(alkoxy styrene), poly(vinyl benzoate), or the like having a syndiotactic tacticity of usually 75 mol % or more, preferably 85 mol % or more in terms of syndiotactic diad (r), or a syndiotactic tacticity of usually 30 mol % or more, preferably 50 mol % or more in terms of syndiotactic pentad (rrrr), a hydrogenated polymer or mixture thereof, or a copolymer containing them as the main component.
[0080] Examples of the poly(hydrocarbon-substituted styrene) include poly(methylstyrene), poly(ethylstyrene), poly(isopropylstyrene), poly(tert-butylstyrene), poly(phenylstyrene), poly(vinylnaphthalene) and poly(vinylstyrene). Examples of the poly(halogenated styrene) include poly(chlorostyrene), poly(bromostyrene) and poly(fluorostyrene), and examples of the poly(halogenated alkylstyrene) include poly(chloromethylstyrene). Examples of the poly(alkoxystyrene) include poly(methoxystyrene) and poly(ethoxystyrene).
[0081] As the comonomer component of the copolymer containing the above-mentioned structural units, in addition to the monomers of the above-mentioned styrene-based polymers, there can be mentioned olefin monomers such as ethylene, propylene, butene, hexene and octene; diene monomers such as butadiene and isoprene; cyclic olefin monomers, cyclic diene monomers, methyl methacrylate, maleic anhydride and acrylonitrile and other polar vinyl monomers.
[0082] As SPS (A), examples of copolymers preferably used include copolymers of styrene and p-methylstyrene, copolymers of styrene and p-tert-butylstyrene, and copolymers of styrene and divinylbenzene. Among them, copolymers of styrene and p-methylstyrene are preferred.
[0083] Among the above-mentioned SPS (A), at least one selected from polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), poly(p-tert-butylstyrene), poly(p-chlorostyrene), poly(m-chlorostyrene), poly(p-fluorostyrene), and copolymers of styrene and p-methylstyrene is preferred; at least one selected from polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), and copolymers of styrene and p-methylstyrene is more preferred; further preferred is polystyrene and a copolymer of styrene and p-methylstyrene; and most preferred is polystyrene.
[0084] Regarding SPS (A), when the melt flow rate (MFR) is measured at a temperature of 300°C and a load of 1.2 kg, it is preferably 8 g / 10 minutes or more, more preferably 10 g / 10 minutes or more, and further preferably 13 g / 10 minutes or more, and preferably 50 g / 10 minutes or less, and more preferably 35 g / 10 minutes or less. If the MFR value of SPS (A) is 8 g / 10 minutes or more, there is no problem with the fluidity of the resin during molding. In addition, if it is 50 g / 10 minutes or less, preferably 35 g / 10 minutes or less, a molded product with sufficient strength can be obtained.
[0085] In the first aspect of the present invention, the weight average molecular weight of SPS (A) is less than 230000. By setting the weight average molecular weight of SPS (A) to less than 230000, the heat resistance and dimensional stability at high temperatures of the fiber-reinforced thermoplastic resin composition of the first aspect of the present invention can be improved, the fluidity of the fiber-reinforced thermoplastic resin composition during molding can be ensured, and the strength of the obtained molded product can be made sufficient.
[0086] From the viewpoint of improving heat resistance and dimensional stability at high temperatures and the fluidity of the resin during molding, the weight average molecular weight of SPS (A) is preferably less than 200,000, preferably less than 190,000, and more preferably less than 185,000. From the viewpoint of improving heat resistance and dimensional stability at high temperatures and the strength of the obtained molded article, the weight average molecular weight of SPS (A) is preferably 10,000 or more, more preferably 50,000 or more, and further preferably 100,000 or more.
[0087] In this specification, unless otherwise specified, the weight average molecular weight refers to a value obtained by measuring by gel permeation chromatography at 145° C. using a GPC apparatus (HLC-8321GPC / HT) manufactured by Tosoh Corporation and a GPC column (GMHHR-H(S)HTC / HT) manufactured by Tosoh Corporation and using 1,2,4-trichlorobenzene as an eluent, and converting using a calibration curve of standard polystyrene.
[0088] Examples of a method for adjusting the weight average molecular weight of SPS (A) include a method of appropriately selecting the type and amount of each catalyst component and the polymerization temperature, and a method of introducing hydrogen.
[0089] The content of the styrene polymer (A) having a syndiotactic structure in 100 parts by mass of the styrene resin composition (S) is 83 to 100 parts by mass. By making the content of the styrene polymer (A) having a syndiotactic structure 83 parts by mass or more, the heat resistance and dimensional stability at high temperatures of the obtained fiber-reinforced thermoplastic resin composition can be improved. The content of the styrene polymer (A) having a syndiotactic structure in 100 parts by mass of the styrene resin composition (S) is preferably 85 to 99 parts by mass, more preferably 86 to 98 parts by mass, and even more preferably 88 to 96 parts by mass.
[0090] SPS (A) can be produced, for example, by polymerizing a styrene-based monomer (a monomer corresponding to the above-mentioned styrene-based polymer) using a titanium compound and a condensation product of water and trialkylaluminum (aluminoxane) as a catalyst in an inert hydrocarbon solvent or in the absence of a solvent (for example, Japanese Patent Application Laid-Open No. 2009-068022).
[0091] <Rubber-like elastic body (B)>
[0092] The fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention may contain the rubber-like elastic body (B) or may not contain the rubber-like elastic body (B).
[0093] By containing the rubber-like elastic body (B) in the fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention, it is possible to improve toughness while maintaining dimensional stability.
[0094] The rubbery elastomer (B) is not limited as long as it is an elastomer containing a structural unit derived from styrene, and is preferably at least one selected from a styrene-diene block copolymer, a hydrogenated styrene-diene block copolymer, a styrene-diene random copolymer, a hydrogenated styrene-diene random copolymer, and a styrene-olefin random copolymer. Here, examples of the diene copolymerized with styrene include butadiene and isoprene, and examples of the olefin copolymerized with styrene include ethylene, propylene, and butene.
[0095] The rubbery elastomer (B) is more preferably at least one selected from the group consisting of styrene-butadiene block copolymers (SBR), hydrogenated styrene-butadiene block copolymers (SEB), styrene-butadiene-styrene block copolymers (SBS), hydrogenated styrene-butadiene-styrene block copolymers (SEBS), styrene-isoprene block copolymers (SIR), hydrogenated styrene-isoprene block copolymers (SEP), styrene-isoprene-styrene block copolymers (SIS), hydrogenated styrene-isoprene-styrene block copolymers (SEPS), styrene-butadiene random copolymers, hydrogenated styrene-butadiene random copolymers, styrene-ethylene-propylene random copolymers, and styrene-ethylene-butylene random copolymers, and is further preferably selected from the group consisting of styrene-butadiene block copolymers (SBR), hydrogenated styrene-butadiene block copolymers (SEB), styrene-butadiene-styrene block copolymers (SBS), hydrogenated styrene-butadiene-styrene block copolymers The present invention is preferably at least one selected from the group consisting of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and more preferably at least one selected from the group consisting of styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and more preferably at least one selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and more preferably hydrogenated styrene-butadiene-styrene block copolymer (SEBS).
[0096] The mass ratio of the structural units derived from styrene and the structural units derived from diene, hydrogenated diene and olefin constituting the rubbery elastomer (B) [(styrene) / (diene, hydrogenated diene, olefin)] is preferably 20 / 80 to 70 / 30, more preferably 25 / 75 to 60 / 40, and even more preferably 25 / 75 to 45 / 55. The styrene content of the rubbery elastomer (B) is preferably in the range of 25 to 60% by mass, and more preferably in the range of 25 to 45%.
[0097] By setting it as such a mass ratio, the compatibility with SPS (A) can be improved, and the toughness can be improved while maintaining the heat resistance and the dimensional stability at high temperature.
[0098] The content of the rubbery elastic body (B) in 100 parts by mass of the styrene resin composition (S) is 0 to 17 parts by mass. By setting the amount of the rubbery elastic body (B) to 17 parts by mass or less, the toughness of the obtained fiber-reinforced thermoplastic resin composition can be improved while maintaining the heat resistance and dimensional stability at high temperatures.
[0099] The content of the rubbery elastic body (B) in 100 parts by mass of the styrene resin composition (S) is preferably 1 to 15 parts by mass, more preferably 2 to 14 parts by mass, and even more preferably 4 to 12 parts by mass.
[0100] <Crystallization nucleating agent (C)>
[0101] The thermoplastic resin composition (T) contains a crystal nucleating agent (C). When the thermoplastic resin composition (T) contains a crystal nucleating agent (C), the crystallization temperature can be increased, the temperature conditions for crystallization can be widely set, and productivity can be improved.
[0102] The crystal nucleating agent is preferably one or more selected from inorganic crystal nucleating agents and organic crystal nucleating agents. Among them, organic crystal nucleating agents are preferred.
[0103] Examples of the organic crystallization nucleating agent include organic carboxylic acid alkali metal salts, organic carboxylic acid alkaline earth metal salts, organic compounds of phosphoric acid or phosphorous acid and metal salts thereof, phthalocyanine derivatives, and sorbitol derivatives.
[0104] More specifically, for example, aluminum di(p-tert-butylbenzoate), sodium salt of benzoic acid, hydroxyaluminum salt of p-tert-butylbenzoate, metal salts of carboxylic acids represented by aluminum hydroxydi(p-tert-butylbenzoate), sodium methylenebis(2,4-di-tert-butylphenol) phosphate, sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl) phosphate, [phosphoric acid [2,2'-methylenebis(4,6-di-tert-butylphenyl)] [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphate] lithium, [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphate] potassium, [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphate] sodium, [[2,4-tert-butylphenyl)]phosphate] sodium, [[4,6',6,6'-tetra-tert-butyl-2,2'-methylenediphenylphosphate]aluminum hydroxide] metal salts of phosphoric acid represented by, [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphate] ammonium, etc. In addition, a complex containing them can also be used. Among them, from the viewpoint of increasing the crystallization temperature, it is preferable to use a lithium salt of an organic compound of phosphoric acid or phosphorous acid, and it is more preferable to use [[2,2'-methylenebis(4,6-di-tert-butylphenyl)]phosphate] lithium.
[0105] In the thermoplastic resin composition (T), the content of the crystallization nucleating agent (C) is 0.6 to 2.0 parts by mass relative to 100 parts by mass of the styrene resin composition (S). By making the content of the crystallization nucleating agent (C) 0.6 parts by mass or more, the crystallization temperature of the obtained fiber-reinforced thermoplastic resin composition can be increased. Therefore, the temperature conditions for crystallizing the fiber-reinforced thermoplastic resin composition can be widely set, so that the conditions for shortening the molding cycle can be selected, and the productivity when used as a reflow-resistant resin material can be improved. In addition, the content of the crystallization nucleating agent (C) relative to 100 parts by mass of the styrene resin composition (S) is 2.0 parts by mass or less, and a crystallization temperature of the fiber-reinforced thermoplastic resin composition sufficient for a reflow-resistant resin material can be obtained.
[0106] The content of the crystal nucleating agent (C) is preferably 0.7 to 1.8 parts by mass, more preferably 0.8 to 1.5 parts by mass, based on 100 parts by mass of the styrene resin composition (S).
[0107] The total content of the styrene resin composition (S) and the crystal nucleating agent (C) in 100% by mass of the thermoplastic resin composition (T) is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and is preferably 100% by mass or less.
[0108] <Modified polyphenylene ether (D)>
[0109] The thermoplastic resin composition (T) contains a modified polyphenylene ether (D). By making the thermoplastic resin composition (T) contain the modified polyphenylene ether (D), the interfacial strength between the thermoplastic resin composition (T) and the glass fiber (G) described later is improved, thereby improving the strength of the fiber-reinforced thermoplastic resin composition. In the thermoplastic resin composition (T), the content of the modified polyphenylene ether (D) is preferably 0.1 to 5.0 parts by mass, more preferably 0.3 to 4.0 parts by mass, further preferably 0.5 to 3.5 parts by mass, and further preferably 1.0 to 3.0 parts by mass, relative to 100 parts by mass of the styrene resin composition (S).
[0110] The modified polyphenylene ether (D) used in the first embodiment of the present invention has compatibility with SPS (A), improves compatibility with other components, and preferably has a polar group that can react with the glass fiber (G).
[0111] Thus, the modified polyphenylene ether (D) is blended for the purpose of improving the compatibility of SPS (A) with other components, especially glass fiber (G), and improving the interfacial strength of each component. More specifically, the modified polyphenylene ether (D) is preferably an acid-modified polyphenylene ether.
[0112] The polar group capable of reacting with the glass fiber (G) refers to a functional group capable of reacting with the polar group possessed by the glass fiber (G). Specific examples thereof include an acid anhydride group, a carboxylic acid group, a carboxylic acid ester group, a carboxylic acid halide group, a carboxylic acid amide group, a carboxylate group, a sulfonic acid group, a sulfonic acid ester group, a sulfonyl chloride group, a sulfonamide group, a sulfonate group, an epoxy group, an amino group, an imide group, an oxazoline group, and the like, preferably a carboxylic acid group.
[0113] As the modified polyphenylene ether (D), fumaric acid-modified polyphenylene ether and maleic anhydride-modified polyphenylene ether are preferred, and fumaric acid-modified polyphenylene ether is more preferred.
[0114] The modification amount (modifier content) of the modified polyphenylene ether (D) is preferably 0.1 to 20% by mass, more preferably 0.2 to 15% by mass, further preferably 0.3 to 10% by mass, and further preferably 0.5 to 5.0% by mass. When the modification amount is within the above range, a styrene resin composition and a molded article having good strength and heat resistance can be obtained.
[0115] The modification amount (modifying agent content) of the modified polyphenylene ether can be determined from the neutralization titration measured in accordance with JIS K 0070-1992.
[0116] Examples of the polyphenylene ether include poly(2,6-dimethyl-1,4-phenylene ether), poly(2,3-dimethyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-chloromethyl-1,4-phenylene ether), poly(2-methyl-6-hydroxyethyl-1,4-phenylene ether), poly(2-methyl-6-n-butyl-1,4-phenylene ether), poly(2-ethyl-6-isopropyl-1,4-phenylene ether), poly(2-ethyl-6-n-propyl-1,4-phenylene ether), poly(2,3,6-trimethyl-1,4-phenylene ether), poly[2-(4'-methylphenyl)-1,4-phenylene ether], poly(2-bromo-6-phenyl-1,4-phenylene ether), and poly(2-methyl-6-phenyl-1,4-phenylene ether). , poly(2-phenyl-1,4-phenylene ether), poly(2-chloro-1,4-phenylene ether), poly(2-methyl-1,4-phenylene ether), poly(2-chloro-6-ethyl-1,4-phenylene ether), poly(2-chloro-6-bromo-1,4-phenylene ether), poly(2,6-di-n-propyl-1,4-phenylene ether), poly(2-methyl-6-isopropyl-1,4-phenylene ether), poly(2-chloro-6-methyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dibromo-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), and the like, preferably poly(2,6-dimethyl-1,4-phenylene ether).
[0117] As the modifier used in the modification of polyphenylene ether, compounds having olefinic double bonds and polar groups in the same molecule can be cited, specifically, for example, maleic anhydride, maleic acid, fumaric acid, maleic esters, fumaric esters, maleimide and its N-substituted product, maleate, fumarate, acrylic acid, acrylate, acrylamide, acrylate, methacrylic acid, methacrylate, methacrylamide, methacrylate, glycidyl methacrylate, etc. can be cited. Among them, maleic anhydride, fumaric acid and glycidyl methacrylate are particularly preferably used, and fumaric acid is more preferably used. The above-mentioned various modifiers can be used alone or in combination of two or more.
[0118] The modified polyphenylene ether (D) can be obtained by reacting the above-mentioned polyphenylene ether with a modifier. The modification method is not particularly limited, and a known method can be used.
[0119] Preferred modification methods include melt modification and solution modification, and melt modification is more preferred from the viewpoint of obtaining a higher modification amount and high productivity. That is, the modified polyphenylene ether (D) is preferably a modified polyphenylene ether produced by melt modification or a modified polyphenylene ether produced by solution modification, and is more preferably a modified polyphenylene ether produced by melt modification.
[0120] Melt modification is a method of obtaining modified polyphenylene ether by melt-kneading polyphenylene ether and a modifier in the presence or absence of a free radical generator. Specifically, it is a method of reacting the polyphenylene ether by melt-kneading at a temperature in the range of 150 to 350° C. using a roll mill, a Banbury mixer, an extruder, or the like.
[0121] Specifically, it is preferred to uniformly dry-mix polyphenylene ether, a modifier, and an optional free radical generator at room temperature, and then perform a melt reaction substantially in the range of 300 to 350° C., which is the kneading temperature of the polyphenylene ether. If the temperature is 300° C. or higher, the melt viscosity can be appropriately maintained, and if the temperature is 350° C. or lower, the decomposition of the polyphenylene ether can be suppressed.
[0122] The amount of the modifier used in the melt modification is preferably 0.1 to 22 parts by mass, more preferably 0.2 to 17 parts by mass, further preferably 0.3 to 12 parts by mass, and further preferably 0.5 to 7.0 parts by mass, relative to 100 parts by mass of the polyphenylene ether. If the amount of the modifier used is within the above range, a styrene resin composition and a molded article having good strength and heat resistance can be obtained.
[0123] The free radical generator used in the melt modification is preferably a free radical generator having a temperature of 300° C. or higher showing a half-life of 1 minute, and specific examples thereof include 2,3-dimethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylhexane, 2,3-dimethyl-2,3-di(p-methylphenyl)butane, etc. Among them, 2,3-dimethyl-2,3-diphenylbutane having a temperature of 330° C. showing a half-life of 1 minute is preferably used.
[0124] The free radical generator is preferably used in an amount of 0.1 to 3 parts by mass, more preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of polyphenylene ether. If it is 0.1 parts by mass or more, a high modification effect can be obtained, and if it is 3 parts by mass or less, the polyphenylene ether can be modified efficiently and insoluble components are not easily generated.
[0125] <Antioxidant (E)>
[0126] From the viewpoint of heat resistance, the thermoplastic resin composition (T) preferably further contains an antioxidant (E). The antioxidant (E) is preferably one or more selected from phenolic compounds, phosphorus compounds and sulfur compounds, and from the viewpoint of heat resistance, phenolic compounds are more preferred.
[0127] Specific examples of the phenolic antioxidant include 2,6-di-tert-butyl-4-methylphenol, 2,6-diphenyl-4-methoxyphenol, 2,2'-methylenebis(6-tert-butyl-4-methylphenol), 2,2'-methylenebis[4-methyl-6-(α-methylcyclohexyl)phenol], 1,1-bis(5-tert-butyl-4-hydroxy-2-methylphenyl)butane, 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-methylenebis(4-methyl-6-nonylphenol), 1,1,3-tris(5-tert-butyl-4-hydroxy-2-methylphenyl)butane, 2,2-bis(5-tert-butyl-4-hydroxy-2-methylphenyl)butane, -4-n-dodecylmercaptobutane, ethylene glycol bis[3,3-bis(3-tert-butyl-4-hydroxyphenyl)butyrate], 1,1-bis(3,5-dimethyl-2-hydroxyphenyl)-3-(n-dodecylthio)butane, 4,4'-thiobis(6-tert-butyl-3-methylphenol), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-2,4,6-trimethylbenzene, 2,2-bis(3,5-di-tert-butyl-4-hydroxybenzyl)malonate, 3-(4-hydroxy-3,5-di-tert-butylphenyl)propionate n-octadecyl, pentaerythritol tetrakis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate}, etc. Pentaerythritol tetrakis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate} is particularly preferred.
[0128] Examples of the phosphorus-based antioxidant include monophosphites such as tris(2,4-di-tert-butylphenyl) phosphite and tris(mononyl- and dinonylphenyl) phosphite, and bisphosphites.
[0129] Examples of the sulfur-based antioxidant include 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], ditridecyl 3,3'-thiodipropionate, and 3,3'-thiodipropionate.
[0130] In the thermoplastic resin composition (T), the content of the antioxidant (E) is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.15 parts by mass or more, relative to 100 parts by mass of the styrene resin composition (S). In addition, it is preferably 2.0 parts by mass or less, more preferably 1.0 parts by mass or less, and further preferably 0.7 parts by mass or less. If the amount of the antioxidant is within the above range, the heat discoloration resistance during processing becomes good, and long-term heat resistance can be obtained, and the oozing of the antioxidant can be suppressed, and the appearance will not be adversely affected.
[0131] <Release agent (F)>
[0132] The thermoplastic resin composition (T) preferably further contains a release agent (F) from the viewpoint of improving heat resistance and dimensional stability at high temperatures. The release agent (F) can be arbitrarily selected from known release agents such as polyethylene wax, silicone oil, and long-chain carboxylic acid.
[0133] In the thermoplastic resin composition (T), the content of the release agent (F) is preferably 0.05 to 3.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, further preferably 0.1 to 1.0 part by mass, and further preferably 0.1 to 0.5 parts by mass, based on 100 parts by mass of the styrene resin composition (S).
[0134] <Glass fiber (G)>
[0135] The fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention contains glass fibers (G) having a flat cross section. When the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention contains glass fibers (G), heat resistance and dimensional stability at high temperatures can be improved.
[0136] In the first embodiment of the present invention, the cross section of the glass fiber (G) perpendicular to the fiber axis is a flat shape. The flat shape refers to a shape in which the profile ratio of the glass fiber (G) is greater than 1. In the first embodiment of the present invention, the profile ratio refers to the ratio of the major diameter to the minor diameter of the cross section perpendicular to the fiber axis of the glass fiber (G), that is, the major diameter / minor diameter. In addition, the major diameter refers to the straight-line distance of the longest distance between two points on the outer edge of the cross section in the cross section perpendicular to the fiber axis, and the minor diameter refers to the straight-line distance between the two points where the straight line perpendicular to the major diameter intersects the outer edge of the cross section. It should be noted that the above-mentioned straight line that becomes the major diameter and the straight line that becomes the minor diameter both pass through the center of gravity of the cross section.
[0137] When the cross section of the glass fiber (G) is flat, the heat resistance of the fiber-reinforced thermoplastic resin composition can be improved, and the dimensional stability at high temperatures can be improved.
[0138] Without being bound by theory, it is speculated that the reason why the heat resistance and dimensional stability at high temperature can be improved by making the cross section of the glass fiber (G) flat is that when the cross section of the glass fiber (G) is flat, it is easy to be oriented in the flow direction (MD) of the resin generated by the rotation of the screw of the extruder kneader, thereby suppressing the breakage of the glass fiber, and the shrinkage is suppressed due to the effect of increasing the aspect ratio of the fiber in the direction perpendicular to the flow direction (TD). From the viewpoint of simultaneously improving heat resistance and dimensional stability at high temperature, the profile ratio of the glass fiber (G) is preferably 2 to 6, more preferably 3 to 5, and further preferably 3.5 to 4.5. The short diameter is preferably 3 μm to 10 μm, and more preferably 5 μm to 8 μm.
[0139] The major axis and minor axis of the glass fiber are both number averages, which are measured by performing image analysis on 50 or more arbitrarily selected glass fibers using a digital microscope and calculated as the number average.
[0140] From the viewpoint of improving dimensional stability at high temperatures, the fiber diameter of the glass fiber (G) is preferably 10 μm or more, more preferably 10.5 μm or more, further preferably 11 μm or more, and further preferably 12 μm or more. In addition, from the viewpoint of ensuring the fluidity of the fiber-reinforced thermoplastic resin composition during molding, the fiber diameter of the glass fiber (G) is preferably 20 μm or less, and more preferably 18 μm or less.
[0141] In the first aspect of the present invention, the fiber diameter of the glass fiber (G) refers to the diameter of a circle obtained by converting a cross section perpendicular to the fiber axis into a circle having the same area as the cross section.
[0142] The fiber diameter of the glass fiber is a number average, and is measured and calculated by performing image analysis on 50 or more arbitrarily selected glass fibers using a digital microscope.
[0143] From the viewpoint of ensuring the fluidity and handleability of the fiber-reinforced thermoplastic resin composition during molding, the fiber length of the glass fiber (G) used in the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention is preferably 1 to 50 mm, more preferably 1.5 to 15 mm, and even more preferably 2 to 8 mm. In addition, the fiber length of the glass fiber (G) contained in the fiber-reinforced thermoplastic resin composition is preferably 300 to 600 μm due to breakage during extrusion kneading.
[0144] The fiber length of the glass fibers is a number average, and is measured and calculated by performing image analysis on 50 or more arbitrarily selected glass fibers using a digital microscope.
[0145] In order to improve the adhesion with SPS (A), the glass fiber (G) is preferably surface-treated with a coupling agent, more preferably treated with a silane coupling agent or a titanium coupling agent, and further preferably treated with a silane coupling agent from the viewpoint of compatibility with the resin component.
[0146] Specific examples of the silane coupling agent include triethoxysilane, vinyl tri(β-methoxyethoxy)silane, γ-methacryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, β-(1,1-epoxycyclohexyl)ethyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ- Mercaptopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl tri(2-methoxyethoxy)silane, N-methyl-γ-aminopropyl trimethoxysilane, N-vinylbenzyl-γ-aminopropyl triethoxysilane, 3-ureidopropyl trimethoxysilane, 3-4,5-dihydroimidazopropyl triethoxysilane, hexamethyldisilazane, N,N-bis(trimethylsilyl)urea, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, etc. Among them, aminosilanes and epoxysilanes such as γ-aminopropyl trimethoxysilane, N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane are preferred.
[0147] Specific examples of titanium coupling agents include triisostearyl isopropyl titanate, tri(dodecylbenzenesulfonyl) isopropyl titanate, tri(dioctylpyrophosphooxy) isopropyl titanate, bis(dioctylphosphite) tetraisopropyl titanate, bis(ditridecylphosphite) tetraoctyl titanate, tetra(1,1-diallyloxymethyl-1-butyl)bis(ditridecyl)phosphite titanate, bis(dioctylpyrophosphooxy) tetraisopropyl titanate, The invention also includes bis(dioctyl pyrophosphoryloxy) glycolate titanate, bis(dioctyl pyrophosphoryloxy) ethylene titanate, trioctyl isopropyl titanate, dimethacryloyl isostearyl titanate isopropyl, isostearyl diacryloyl titanate isopropyl, tri(dioctylphosphoryloxy) isopropyl titanate, tricumylphenyl isopropyl titanate, tri(N-amidoethyl, aminoethyl) isopropyl titanate, dicumylphenyl glycolate titanate, diisostearyl titanate ethylene, etc. Among them, tri(N-amidoethyl, aminoethyl) isopropyl titanate is preferred.
[0148] In the total of 100 mass % of the thermoplastic resin composition (T) and the glass fiber (G), the content of the glass fiber (G) in the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention is 33.0 mass % or more and 65.0 mass % or less. By making the content of the glass fiber (G) 33.0 mass % or more, the heat resistance and the dimensional stability at high temperature can be improved, and the toughness required for the molded body for reflow soldering or the connector for reflow soldering can be obtained. By making the content of the glass fiber (G) 65.0 mass % or less, the fluidity of the fiber-reinforced thermoplastic resin composition during molding can be ensured, and the tensile fracture strain reaches 1.0% or more, and the toughness required for the molded body for reflow soldering or the connector for reflow soldering can be obtained.
[0149] The content of the glass fiber (G) in the fiber-reinforced thermoplastic resin composition is preferably 33.0 mass % to 65.0 mass %, more preferably 35.0 mass % to 58.0 mass %, further preferably 38.0 mass % to 55.0 mass %.
[0150] <Other ingredients>
[0151] To the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention, other optional components may be added within a range that does not hinder the purpose of the first embodiment of the present invention.
[0152] As other components, a colorant, a crosslinking agent, a crosslinking auxiliary agent, a dispersant, a plasticizer, an antifouling agent, an ultraviolet absorber, a light stabilizer, a flame retardant, a flame retardant auxiliary agent, an antistatic agent, and the like may be contained as optional components.
[0153] ≪Coloring agent≫
[0154] As the colorant, any known colorant such as carbon black, inorganic colorant, organic colorant, etc. can be selected and used. As the inorganic colorant, inorganic pigments can be mentioned, and as the organic colorant, organic pigments and organic dyes can be mentioned. Inorganic pigments can be mentioned titanium dioxide, iron oxide, nickel titanium yellow, zinc sulfide, barium sulfate, ultramarine. Organic pigments are at least one selected from monoazo pigments, perylene pigments, quinacridone pigments and phthalocyanine pigments. Specific examples of suitable organic pigments include monoazo pigments such as Pigment Yellow 183 and Pigment Yellow 150, perylene pigments such as Pigment Red 178 and Pigment Red 149, quinacridone pigments such as Pigment Violet 19, Pigment Red 122, Pigment Red 209, Pigment Red 202, Pigment Orange 48 and Pigment Orange 49, and phthalocyanine pigments such as Pigment Blue 15, Pigment Blue 16, Pigment Green 7 and Pigment Green 36.
[0155] ≪Dispersant≫
[0156] The dispersant may be arbitrarily selected from known dispersants such as methylenebisstearic acid amide, polyacrylic acid, sodium polyacrylate, sodium carboxylate, ammonium polyacrylate, polyacrylic acid copolymers, sodium polycarboxylates, carboxylic acid copolymers, and sulfonic acid copolymers.
[0157] ≪Ultraviolet absorber≫
[0158] As the ultraviolet absorber, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-tert-butyl-4-methylphenol, 2-(4,6-diphenyl-1,3, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetrazine, 2-(2H-benzotriazol-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol, 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, [2-hydroxy-4-(octyloxy)phenyl](phenyl)methanone ramethylbutyl)phenol, 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol] , 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(5-chloro-2H-benzotriazol-2-yl)-6-tert-butyl-4-methylphenol, 2-(4,6 -diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol, 2,4,6-tris(2-hydroxy-4-hexylox Any known ultraviolet absorbers such as (y-3-methylphenyl)-1,3,5-triazine and [2-hydroxy-4-(octyloxy)phenyl](phenyl)methanone) can be used.
[0159] ≪Light Stabilizer≫
[0160] As a light stabilizer, tetrakis (1,2,2,6,6-pentamethyl-4-piperidinyl) butane-1,2,3,4-tetracarboxylate, tetrakis (2,2,6,6-tetramethyl-4-piperidinyl) butane-1,2,3,4-tetracarboxylate; 1,2,3,4-butanetetracarboxylic acid, tetramethyl ester, and 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5 ]Undecane-3,9-diethanol reaction products; 1,2,3,4-butanetetracarboxylic acid, tetramethyl ester, reaction products with 2,2,6,6-tetramethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol; bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate 、bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate、1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate、2,2,6,6-tetramethyl-4-piperidinyl methacrylate、2,2,6,6-tetramethylpiperidin-4-yl hexadecanoate、2,2,6,6-tetramethylpiperidin-4-yl octadecanoate (English original: tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate、tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate、1,2,3,4-butanetetracarboxylic acid, tetramethyl ester, reaction products with 1,2,2,6,6-pentamethyl-4-piperidinoland β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5] undecane-3,9-diethanol, 1,2,3,4-butanetetracarboxylic acid, tetramethyl ester, reaction products with2,2,6,6-tetramethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5] undecane-3,9-diethanol, bis (1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, bis (2,2,6,6-tetramethyl-4-piperid yl) sebacate, bis (1-undecanoxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, 1,2,2,6,6-pentamethyl-4-piperidyl Any well-known light stabilizer such as methacrylate, 2,2,6,6-tetramethyl-4-piperidyl methacrylate, 2,2,6,6-tetramethylpiperidin-4-yl hexadecanoate, 2,2,6,6-tetramethylpiperidin-4-yloctadecanoate) can be selected and used. .
[0161] ≪Flame retardant≫
[0162] As the flame retardant, any flame retardant selected from known flame retardants such as brominated polystyrene, ethylenebis(pentabromophenyl), ethylenebis(tetrabromophthalimide), polypentabromobenzyl acrylate, tetrabromobisphenol A, condensed phosphate esters, ammonium polyphosphate, phosphonates, phosphites, melamine cyanurate, magnesium hydroxide, and boehmite can be used.
[0163] ≪Flame retardant additives≫
[0164] As the flame retardant aid, any flame retardant aid may be selected and used from known flame retardants such as antimony trioxide, sodium antimonate, antimony pentoxide, zinc borate, and hydrotalcite.
[0165] [Physical properties of fiber-reinforced thermoplastic resin compositions]
[0166] In the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention, the deflection temperature under load is preferably 255° C. or higher, more preferably 258° C. or higher, further preferably 260° C. or higher, and further preferably 262° C. or higher. By setting the deflection temperature under load to 255° C. or higher, the heat resistance of the obtained molded article can be made sufficient.
[0167] The deflection temperature under load can be adjusted by the content of the glass fiber (G), the profile ratio of the glass fiber (G), the total mass ratio of the structural unit derived from styrene and other structural units constituting the rubbery elastomer (B), the content of the rubbery elastomer (B), etc.
[0168] In the first aspect of the present invention, the deflection temperature under load can be measured by a method in accordance with Method A of ISO 527-1, 2 (2020), and can be measured by the method described in Examples.
[0169] In the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention, the reflow shrinkage in MD is preferably 0.10% or less, and more preferably 0.08% or less. In addition, the reflow shrinkage in TD is preferably 0.20% or less, and more preferably 0.16% or less. In addition, the anisotropy of the reflow shrinkage (TD / MD) is preferably 4.5 or less, more preferably 3.0 or less, more preferably 2.2 or less, and more preferably 1.8 or less.
[0170] If the reflow shrinkage in each direction and the anisotropy of the reflow shrinkage are within the above ranges, it can be said that the dimensional stability at high temperature is high. When the connector using the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention is used in the reflow process, the dimensional stability at high temperature is high, so that the dimensional change and warping of the connector can be suppressed, and the poor fitting with the harness connector can be prevented, and the change in the distance between the solder paste coated portion of the substrate and the metal terminal of the connector can be suppressed to prevent poor joining.
[0171] The reflow shrinkage in each direction and the anisotropy of the reflow shrinkage can be adjusted by, for example, the content of the glass fiber (G) and the profile ratio of the glass fiber (G).
[0172] In the first aspect of the present invention, the anisotropy of the reflow shrinkage (TD / MD) is obtained as a ratio of the dimensional change in MD (reflow shrinkage in MD) and the dimensional change in TD (reflow shrinkage in TD) of the test piece before and after the reflow process (reflow shrinkage in TD / reflow shrinkage in MD). MD refers to the flow direction of the resin during molding, and TD refers to the direction perpendicular to the flow direction.
[0173] In addition, the shrinkage rate of the reflow treatment in each direction in the first embodiment of the present invention is measured by the method described in the embodiment using a test piece. The test piece can be processed and measured according to IEC60068-2-58 as described in the embodiment. As a test piece used in the measurement of the shrinkage rate of the reflow treatment in each direction, for example, a test piece of a square plate of 80 mm×80 mm×2 mm in thickness can be used.
[0174] In the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention, the SFL (Spiral Flow Length) when molding is performed using a spiral flow die with a flow path thickness of 1 mm and a width of 10 mm and an injection pressure of 100 MPa is preferably 100 mm or more, more preferably 130 mm or more, further preferably 140 mm or more, and further preferably 150 mm or more. By setting the SFL to 100 mm or more, the fluidity of the fiber-reinforced thermoplastic resin composition during molding can be fully ensured. In addition, the SFL is preferably 185 mm or less.
[0175] SFL can be adjusted by, for example, the content of the glass fiber (G) and the weight average molecular weight of the styrene polymer (A) having a syndiotactic structure.
[0176] In addition, in the first aspect of the present invention, SFL can be measured by the method described in the Examples.
[0177] In the fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention, the tensile breaking stress is preferably 110 MPa or more, more preferably 120 MPa or more, and even more preferably 130 MPa or more.
[0178] The tensile fracture strain is preferably 1.0% or more, more preferably 1.2% or more, further preferably 1.3% or more, and further preferably 1.4% or more.
[0179] By setting the tensile fracture stress to 110 MPa or more and the tensile fracture strain to 1.0% or more, the toughness of the obtained formed body can be made sufficient.
[0180] The tensile breaking stress and tensile breaking strain can be adjusted by, for example, the content of the glass fiber (G), the total mass ratio of the structural unit derived from styrene and other structural units constituting the rubbery elastomer (B), the content of the rubbery elastomer (B), etc.
[0181] In the first embodiment of the present invention, the tensile stress at break and the tensile strain at break can be measured by a method in accordance with ISO 527-1, 2: 2019, and can be measured by the method described in the Examples.
[0182] The fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention preferably has a crystallization temperature of 246° C. or higher. By setting the crystallization temperature within the above range, productivity can be improved when using the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention as a reflow-resistant resin material to produce a molded body.
[0183] The crystallization temperature can be adjusted by, for example, the content and type of the crystal nucleating agent (C).
[0184] In addition, in the first aspect of the present invention, the crystallization temperature can be measured by the method described in the examples.
[0185] [Manufacture of fiber-reinforced thermoplastic resin composition]
[0186] The fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention is a composition obtained by blending and kneading a styrene resin (A) having a syndiotactic structure, a rubbery elastomer (B), a crystal nucleating agent (C), and glass fibers (G), and, if necessary, the above-mentioned modified polyphenylene ether (D), an antioxidant (E), a release agent (F), and other components.
[0187] The compounding and kneading can be carried out by premixing using commonly used equipment such as a ribbon mixer, a tumbler, a Henschel mixer, etc., using a Banbury mixer, a single-screw extruder, a twin-screw extruder, a multi-screw extruder, a co-kneader, etc.
[0188] The melt-kneaded fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention is preferably stored in a pellet form and used as a reflow-resistant resin material.
[0189] [Reflow resistant resin material]
[0190] In the first aspect of the present invention, the reflow resistance means having sufficient reflow heat resistance to withstand the reflow process, and the reflow heat resistance can be evaluated by the deflection temperature under load and the reflow shrinkage rate described above.
[0191] The first embodiment of the present invention comprises a reflow-resistant resin material comprising the fiber-reinforced thermoplastic resin composition. That is, the first embodiment of the present invention comprises a fiber-reinforced thermoplastic resin composition, wherein the fiber-reinforced thermoplastic resin composition comprises a thermoplastic resin composition (T) and a glass fiber (G) having a flat cross section, wherein the thermoplastic resin composition (T) comprises 100 parts by mass of a styrene-based resin composition (S) and 0.6 to 2.0 parts by mass of a crystal nucleating agent (C), wherein the styrene-based resin composition (S) comprises 83 to 100 parts by mass of a styrene-based polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 0 to 17 parts by mass of a rubber-like elastic body (B), and the content of the glass fiber (G) is 33.0 to 65.0% by mass relative to the total of the thermoplastic resin composition (T) and the glass fiber (G).
[0192] As reflow soldering processes, there are "insert mounting (IMT: Insertion Mount Technology)" and "surface mounting (SMT: Surface Mount Technology)" represented by through-hole reflow, wherein the through-hole reflow is to fill the holes (through-holes) formed in the metal circuit part of the printed circuit board with solder paste, pass the metal terminals of the connector, etc. through the holes, and then heat and solder them in a reflow oven, while the surface mounting is to apply solder paste to the metal circuit part on the printed circuit board, place the metal terminals of the connector, etc. on it, and then heat and solder them in a reflow oven.
[0193] Among them, in particular, since surface mounting is performed by soldering metal terminals of connectors, etc. on solder paste applied to the surface of a printed circuit board, poor bonding may sometimes occur due to reasons such as changes in the distance between the surface of the printed circuit board and the metal terminals of the connector, etc., caused by changes in the dimensions of the printed circuit board, connector, etc. at high temperatures.
[0194] On the other hand, since the reflow-resistant resin material according to the first aspect of the present invention includes the fiber-reinforced thermoplastic resin composition, it is excellent in heat resistance and dimensional stability at high temperatures.
[0195] Therefore, the reflow soldering resistant resin material of the first embodiment of the present invention can be used in the reflow soldering process, and has excellent dimensional stability in the reflow soldering process based on surface mounting. In addition, by using the reflow soldering resistant resin material of the first embodiment of the present invention as a part of a printed circuit board, a connector, etc., it is possible to suppress their dimensional changes and prevent poor bonding, which is more suitable.
[0196] The reflow-resistant resin material of the first embodiment of the present invention may contain other thermoplastic resins, etc., within the range that does not impair the effect of the first embodiment of the present invention, but the reflow-resistant resin material of the first embodiment of the present invention is substantially formed by the above-mentioned fiber-reinforced thermoplastic resin composition. Specifically, the content of the above-mentioned fiber-reinforced thermoplastic resin composition in the reflow-resistant resin material of the first embodiment of the present invention is preferably 90% by mass or more, more preferably 95% by mass or more, and further preferably 99% by mass or more. There is no upper limit, as long as it is 100% by mass or less, preferably 100% by mass, and it may also be composed only of the above-mentioned fiber-reinforced thermoplastic resin composition.
[0197] As described above, the first embodiment of the present invention has excellent heat resistance and dimensional stability at high temperatures, and can therefore be suitably used for forming a molded body. The shape of the molded body is not particularly limited, and examples thereof include injection molded products and extrusion molded products. As described above, the resin member formed by the first embodiment of the present invention can be suitably used in the reflow soldering process, and therefore, the first embodiment of the present invention can be particularly suitably used for molded bodies and connectors for reflow soldering.
[0198] The molded body for reflow soldering of the first embodiment of the present invention is composed of the above-mentioned reflow-resistant resin material. Therefore, as described above, it has excellent heat resistance and dimensional stability at high temperatures, and can be particularly preferably used as a resin-metal composite composed of the molded body for reflow soldering of the first embodiment of the present invention and a metal member.
[0199] A resin-metal composite according to a first aspect of the present invention is formed of the above-mentioned molded body for reflow soldering and a metal member.
[0200] Furthermore, a connector according to a first aspect of the present invention is formed of the above-mentioned resin-metal composite.
[0201] As described above, the molded body for reflow soldering, the resin-metal composite, and the connector according to the first aspect of the present invention have excellent heat resistance and dimensional stability at high temperatures. Therefore, when the molded body for reflow soldering, the resin-metal composite, and the connector according to the first aspect of the present invention are used in a reflow soldering process, the bonding strength with the substrate can be improved. Therefore, even when stress is biasedly applied to one or an end of the bonding surface, the bonding portion is not easily broken.
[0202] As the metal member of the resin-metal composite of the first embodiment of the present invention, at least one selected from aluminum, stainless steel, copper, titanium and alloys thereof is preferably used. These metals can be selected according to the intended use and physical properties, and copper or a copper alloy is more preferably used.
[0203] The shape of the metal component is not particularly limited as long as it can be joined to the above-mentioned reflow soldering molded body. For example, it can be made into a flat plate, a curved plate, a rod, a cylinder, a block, etc. It can also be a structure composed of a combination of them. The shape of the surface of the joint of the metal component joined to the reflow soldering molded body of the first embodiment of the present invention is not particularly limited, and a plane, a curved surface, etc. can be cited. On the other hand, in order to maintain the bonding strength, it is more preferably set to a shape that is not easy to concentrate stress.
[0204] [Reflow soldering process]
[0205] As the reflow soldering process of the first embodiment of the present invention, it is possible to appropriately select a reflow soldering process based on "insert mounting" in which the pins of the chip component of the connector of the first embodiment of the present invention are passed through holes (through holes) formed in the joint portion of the printed circuit board, the hole portion is filled with a reflow soldering material, and then the hole portion is heated in a reflow soldering furnace and soldered, or a reflow soldering process based on "surface mounting" in which solder paste is applied to the joint portion of the printed circuit board where there is no hole, the connector of the first embodiment of the present invention is placed, and then the hole portion is heated in a reflow soldering furnace and soldered.
[0206] As described above, the molded body for reflow soldering according to the first aspect of the present invention has excellent heat resistance and dimensional stability at high temperatures, so when it is made into a resin-metal composite, it is possible to suppress the stress from being concentrated on a part of the joint surface between the resin member and the metal member, and the joint portion is not easily damaged. Therefore, the resin-metal composite formed of the molded body for reflow soldering and the metal member according to the first aspect of the present invention, and the connector formed of the resin-metal composite, can suppress the displacement of the joint portion caused by the dimensional change of the molded body and the stress concentration, and prevent poor bonding, especially in the reflow soldering process based on "surface mounting".
[0207] Therefore, the resin-metal composite according to the first aspect of the present invention is preferably used in a reflow soldering process, and more preferably used in a reflow soldering process for surface mounting.
[0208] Furthermore, as described above, the molded body for reflow soldering according to the first aspect of the present invention has excellent heat resistance and dimensional stability at high temperatures. Therefore, the resin-metal composite according to the first aspect of the present invention and the connector according to the first aspect of the present invention can also be used in a low-silver lead-free reflow soldering process using a low-silver lead-free solder in which the amount of added silver that lowers the melting point of the lead-free solder is reduced.
[0209] [Resin-metal composite according to the second aspect of the present invention]
[0210] The resin-metal composite of the second embodiment of the present invention comprises a resin member and a metal member, wherein the resin member is formed of a reinforced thermoplastic resin composition comprising a thermoplastic resin composition (T2) and a glass filler (G2), and the linear expansion coefficient (CTE) of the TD of the resin member is TD ) and the linear expansion coefficient (CTE) of the above metal components M ) (CTE TD -CTE M ) is 6.0×10 -5 / °C or less, and a flexural fracture strain of a parallel flow welded test piece formed of the reinforced thermoplastic resin composition (hereinafter also referred to as “parallel flow welded flexural fracture strain”) is 1.15% or more.
[0211] Generally, in a resin-metal composite, when exposed to an environment with a large temperature change, if the difference between the linear expansion coefficient of the resin member and the linear expansion coefficient of the metal member is large, the strain between the resin member and the metal member becomes large, and damage such as cracks is easily generated. In other words, the resin-metal composite becomes insufficient in thermal shock resistance.
[0212] Generally, the linear expansion coefficient of a molded body of a resin reinforced with fibers or the like greatly differs between the flow direction (MD) of the resin during molding and the direction (TD) perpendicular to the flow of the resin, and the linear expansion coefficient of TD is larger than that of MD. Therefore, in a resin-metal composite, when comparing the linear expansion coefficients of a resin member and a metal member, the difference between the linear expansion coefficient of TD of the resin member and the linear expansion coefficient of the metal member becomes particularly large compared to the difference between the linear expansion coefficient of MD and the linear expansion coefficient of the metal member. As a result, it is believed that when the resin-metal composite is exposed to an environment with a large temperature change, the strain in TD becomes particularly large, and cracks are likely to occur.
[0213] Therefore, the present inventors have found that in a resin-metal composite, by adjusting the linear expansion coefficient (CTE) of the TD of the resin member TD ) and the linear expansion coefficient (CTE) of the above metal components M ) (CTE TD -CTE M ) is reduced to below a certain range, thereby improving the heat shock resistance.
[0214] On the other hand, it was confirmed that even if CTE TD -CTE M When the CTE is reduced to below a certain range, it may be damaged when exposed to an environment with large temperature changes. The inventors of the present invention have conducted in-depth research and found that parallel flow welding is particularly related to thermal shock resistance. TD -CTE M By reducing it to a certain range or less and setting the bending fracture strain of the parallel flow welding to a specific value or more, excellent thermal shock resistance can be obtained.
[0215] In the resin-metal composite of the second embodiment of the present invention, by TD -CTE M The reason why excellent thermal shock resistance can be obtained by reducing the stress to a certain range or less and setting the bending fracture strain of co-flow welding to a specific value or more is not clear, but the inventors speculate as follows.
[0216] It is known that the weld is formed at the part where the resin flows together and is more fragile than other parts. According to its formation process, it is divided into counter-flow weld and parallel flow weld. The counter-flow weld is a weld formed at the part where the flow directions of the resin are opposite to each other during molding. It is believed that it is easily affected by the expansion and contraction of the MD of the resin component during the thermal shock test (or when the ambient temperature changes). On the other hand, the parallel flow weld is a weld formed at the part where the flow directions of the resin are parallel during molding. It is believed that it is easily affected by the expansion and contraction of the TD of the resin component during the thermal shock test (or when the ambient temperature changes).
[0217] In the resin-metal composite, the parallel flow welded portion formed by the flow of the resin in parallel and converging during molding is greatly affected by the expansion and contraction of TD. It is believed that the linear expansion coefficient of TD of the resin component is greater than the linear expansion coefficient of MD. Therefore, at the parallel flow welded portion of the resin-metal composite, the strain with the metal component becomes large, and the resin component becomes easily damaged. It is believed that by increasing the CTE TD -CTE M Set to 6.0×10 -5 / °C or less, and further, the bending fracture strain of the parallel flow welding is set to a range of 1.15% or more, so that the resin-metal composite can withstand the strain between the resin member and the metal member even when exposed to an environment with a large temperature change, so that the stress applied to the parallel flow welded portion that is easily damaged is relaxed, and as a result, a resin-metal composite having excellent heat shock resistance can be obtained.
[0218] As described above, the second embodiment of the present invention is to adjust the linear expansion coefficient (CTE) of the TD of the resin member. TD ) and the linear expansion coefficient (CTE) of the metal component M ) (CTE TD -CTE M ) is set to 6.0×10 -5 / °C or less, and the bending fracture strain of the parallel flow welded test piece formed of the reinforced thermoplastic resin composition is set to 1.15% or more, thereby achieving excellent thermal shock resistance.
[0219] Hereinafter, each item will be described in detail.
[0220] 〔Linear expansion coefficient〕
[0221] In the resin-metal composite according to the second aspect of the present invention, the linear expansion coefficient (CTE) of the TD of the resin member TD ) and the linear expansion coefficient (CTE) of the metal component M ) (CTE TD -CTE M ) is 6.0×10 -5 / °C or less, preferably 5.9×10-5 / ℃ or less. By making CTE TD -CTE M 6.0×10 -5 / °C or less, the strain between the resin member and the metal member can be reduced, and the thermal shock resistance can be improved.
[0222] In addition, about CTE TD -CTE M The lower limit of is not particularly limited, but is preferably 0 / °C or higher from the viewpoint of reducing the strain between the resin member and the metal member and suppressing the destruction of the resin-metal composite. In addition, from the viewpoint of achieving both the thermal shock resistance of the resin-metal composite and the elongation at break, formability, and kneading stability of the resin member, it is more preferably 1.5×10 -5 / °C or more, more preferably 2.0×10 -5 / °C or more, and more preferably 2.5×10 -5 / ℃ or above.
[0223] In the second aspect of the present invention, the linear expansion coefficient can be measured by the method described in Examples.
[0224] The coefficient of linear expansion (CTE) of the resin component TD ) Although it depends on the combination with metal components, it can reduce CTE TD -CTE M , from the viewpoint of improving the heat shock resistance of the resin-metal composite, preferably 8.5×10 -5 / °C or less, more preferably 8.0×10 -5 / ℃ or less. About CTE TD The lower limit of is not particularly limited, but is preferably 2.0×10 -5 / ℃ or above.
[0225] The coefficient of linear expansion (CTE) of the resin component TD ) can be adjusted by the type and content of the glass filler (G2) contained in the resin member. The present inventors have found that the glass filler (G2) in the resin member has a CTE of 1.170° by making it into a glass fiber or glass sheet with a flat cross section. TD In addition, it was found that by increasing the content of glass filler (G2) in the resin component, the CTE TD The trend of getting smaller.
[0226] The coefficient of linear expansion (CTE) of metal components M ) is not particularly limited, but is preferably 0.5×10 -5 ~3.0×10-5 / °C, more preferably 1.0×10 -5 ~2.8×10 -5 / °C, more preferably 1.5×10 -5 ~2.5×10 -5 / ℃.
[0227] The coefficient of linear expansion (CTE) of metal components M ) can be adjusted according to the type of metal used in the metal component, etc.
[0228] [Bending fracture strain of parallel flow welded test piece formed of reinforced thermoplastic resin composition]
[0229] In the resin-metal composite of the second aspect of the present invention, the bending fracture strain of the parallel flow welded test piece formed of the reinforced thermoplastic resin composition (bending fracture strain of parallel flow welding) is 1.15% or more, preferably 1.20% or more. By setting the bending fracture strain of parallel flow welding to 1.15% or more, the stress between the resin member and the metal member can be relaxed, and the thermal shock resistance can be improved.
[0230] The upper limit of the bending fracture strain in the parallel flow welding is not particularly limited, but is preferably 2.00% or less from the viewpoint of achieving a balance between the thermal shock resistance of the resin-metal composite and the elastic modulus and heat resistance of the resin member.
[0231] The bending fracture strain of parallel flow welding can be adjusted by the contents of the rubber-like elastic body (B) and the release agent (F) contained in the resin member, etc. The bending fracture strain of parallel flow welding tends to increase by increasing the content of the rubber-like elastic body (B) contained in the resin member.
[0232] In the second embodiment of the present invention, the bending fracture strain of the parallel flow weld can be derived using a test piece obtained from a molded body for measurement, wherein the molded body for measurement has a parallel flow weld portion formed of a reinforced thermoplastic resin composition. The measurement is performed using a parallel flow weld test piece, which is a parallel flow weld test piece of a reinforced thermoplastic resin composition having a width of 10 mm, a length of 80 mm, and a thickness of 2 mm cut out at a position 50 to 60 mm from the gate portion of the molded body for measurement on the MD. Specifically, a parallel flow weld test piece is obtained from a molded body for measurement, wherein the parallel flow weld test piece is a parallel flow weld test piece of a reinforced thermoplastic resin composition having a width of 10 mm, a length of 80 mm, and a thickness of 2 mm. Figure 1 The measurement molded body 1 shown is a test piece cut out from the cutout portion 11 of the co-flow welded bending fracture strain measurement test piece for measurement.
[0233] The molded body 1 for measurement passes Figure 2 and Figure 3 The mold 2 for the measuring molded body shown is made. Figure 3As shown in FIG. 2 , the mold 2 is provided with a partition wall 25. The partition wall 25 allows the reinforced thermoplastic resin composition introduced from the resin introduction port 24 to be divided into flow paths A and B and flow in the cavity 23. Then, the reinforced thermoplastic resin composition divided into flow paths A and B and flowing merges at the resin confluence portion 26 in the cavity 23 to form a weld. At this time, regarding the weld near the partition wall 25, since the flows of the merged resins are opposite, a counter-flow weld is formed. On the other hand, at a position away from the partition wall 25, more specifically, at a position farther than 50 mm in MD from the partition wall 25, the flows of the merged resins are parallel, so a parallel flow weld is formed.
[0234] Therefore, since the parallel flow welded test piece formed of the reinforced thermoplastic resin composition in the second aspect of the present invention has a parallel flow weld portion, the bending fracture strain of the parallel flow weld portion, which is the purpose of the second aspect of the present invention, can be measured.
[0235] In the second aspect of the present invention, the bending fracture strain of the parallel flow welding is measured using the parallel flow welding test piece formed of the reinforced thermoplastic resin composition in accordance with ISO178:2010, specifically, by the method described in the Examples.
[0236] 〔Resin components〕
[0237] In the resin-metal composite according to the second aspect of the present invention, the resin member is formed of a reinforced thermoplastic resin composition containing a thermoplastic resin composition (T2) and a glass filler (G2).
[0238] <Thermoplastic resin composition (T2)>
[0239] In the resin-metal composite of the second embodiment of the present invention, the thermoplastic resin composition (T2) preferably includes a styrene resin composition (S2) composed of 75 to 94 parts by mass of a styrene polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 6 to 25 parts by mass of a rubbery elastomer (B).
[0240] <Styrene polymer having a syndiotactic structure (A)>
[0241] In the resin-metal composite of the second embodiment of the present invention, the styrene polymer (A) having a syndiotactic structure (hereinafter also referred to as SPS (A)) is a styrene resin having a high syndiotactic structure, and is preferably the same styrene resin as the SPS (A) exemplified in the first embodiment of the present invention.
[0242] The SPS (A) is preferably one or more selected from polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), poly(p-tert-butylstyrene), poly(p-chlorostyrene), poly(m-chlorostyrene), poly(p-fluorostyrene), and a copolymer of styrene and p-methylstyrene; more preferably one or more selected from polystyrene, poly(p-methylstyrene), poly(m-methylstyrene), and a copolymer of styrene and p-methylstyrene; further preferably polystyrene and a copolymer of styrene and p-methylstyrene; and most preferably polystyrene.
[0243] When the melt flow rate (MFR) of SPS (A) is measured at a temperature of 300° C. and a load of 1.2 kg, it is preferably 8 g / 10 minutes or more, more preferably 10 g / 10 minutes or more, and further preferably 13 g / 10 minutes or more, and is preferably 50 g / 10 minutes or less, and more preferably 35 g / 10 minutes or less. When the MFR value of SPS (A) is 8 g / 10 minutes or more, there is no problem with the fluidity of the resin during molding of the resin-metal composite, and when it is 50 g / 10 minutes or less, the strength of the resin-metal composite can be made sufficient, and the heat shock resistance can be improved.
[0244] In the resin-metal composite of the second aspect of the present invention, the weight average molecular weight of SPS (A) is preferably less than 230,000, more preferably less than 200,000, further preferably less than 190,000, further preferably less than 185,000, and is preferably 10,000 or more, more preferably 50,000 or more, and further preferably 100,000 or more. When the weight average molecular weight of SPS (A) is less than 230,000, there is no problem with the fluidity of the resin during molding of the resin-metal composite, and when it is 10,000 or more, the strength of the resin-metal composite can be made sufficient and the heat shock resistance can be improved.
[0245] Examples of a method for adjusting the weight average molecular weight of SPS (A) include the same method as that for SPS (A) exemplified in the first aspect of the present invention.
[0246] The content of SPS (A) in 100 parts by mass of the styrene resin composition (S2) is preferably 75 to 94 parts by mass, more preferably 77 to 93 parts by mass, further preferably 78 to 92 parts by mass, and further preferably 79 to 91 parts by mass. When the content of SPS (A) is within the above range, the heat shock resistance of the resin-metal composite can be improved.
[0247] SPS (A) can be produced by polymerizing a styrene monomer or the like in the same manner as the method exemplified in the first embodiment of the present invention.
[0248] <Rubber-like elastic body (B)>
[0249] In the resin-metal composite of the second aspect of the present invention, the thermoplastic resin composition (T2) contains the rubber-like elastomer (B), so that the toughness of the resin member can be improved, in particular, the bending fracture strain of parallel flow welding can be increased, and the heat shock resistance of the resin-metal composite can be improved.
[0250] As the rubbery elastic body (B), the same rubbery elastic body (B) as exemplified in the first aspect of the present invention is preferred.
[0251] The rubbery elastomer (B) is more preferably at least one selected from the group consisting of styrene-butadiene block copolymers (SBR), hydrogenated styrene-butadiene block copolymers (SEB), styrene-butadiene-styrene block copolymers (SBS), hydrogenated styrene-butadiene-styrene block copolymers (SEBS), styrene-isoprene block copolymers (SIR), hydrogenated styrene-isoprene block copolymers (SEP), styrene-isoprene-styrene block copolymers (SIS), hydrogenated styrene-isoprene-styrene block copolymers (SEPS), styrene-butadiene random copolymers, hydrogenated styrene-butadiene random copolymers, styrene-ethylene-propylene random copolymers and styrene-ethylene-butylene random copolymers, and is further preferably selected from the group consisting of styrene-butadiene block copolymers (SBR), hydrogenated styrene-butadiene block copolymers (SEB), styrene-butadiene-styrene block copolymers (SBS), hydrogenated styrene-butadiene-styrene block copolymers The present invention is preferably at least one selected from the group consisting of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (SEP), styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and is further preferably at least one selected from the group consisting of styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and is further preferably at least one selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymer (SEBS) and styrene-isoprene-styrene block copolymer (SIS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and is further preferably hydrogenated styrene-butadiene-styrene block copolymer (SEBS).
[0252] The mass ratio of the structural units derived from styrene and the structural units derived from diene, hydrogenated diene and olefin constituting the rubbery elastomer (B) [(styrene) / (diene, hydrogenated diene, olefin)] is preferably 20 / 80 to 70 / 30, more preferably 25 / 75 to 60 / 40, and even more preferably 25 / 75 to 45 / 55. The styrene content of the rubbery elastomer (B) is preferably in the range of 25 to 60% by mass, and more preferably in the range of 25 to 45%.
[0253] By setting such a mass ratio, the compatibility with SPS (A) can be improved, and the thermal shock resistance of the resin-metal composite can be improved.
[0254] The content of the rubbery elastic body (B) in 100 parts by mass of the styrene resin composition (S2) is preferably 6 to 25 parts by mass, more preferably 7 to 20 parts by mass, further preferably 8 to 15 parts by mass, and further preferably 8 to 12 parts by mass. When the content of the rubbery elastic body (B) is within the above range, the heat shock resistance of the resin-metal composite can be improved.
[0255] <Crystallization nucleating agent (C)>
[0256] In the resin-metal composite of the second aspect of the present invention, the thermoplastic resin composition (T2) preferably further contains a crystallization nucleating agent (C). By making the thermoplastic resin composition (T2) contain a crystallization nucleating agent (C), the crystallization temperature can be increased, the temperature conditions for crystallization can be widely set, and productivity can be improved.
[0257] In addition, in the thermoplastic resin composition (T2), the content of the crystallization nucleating agent (C) is preferably 0.6 to 2.0 parts by mass, more preferably 0.7 to 1.8 parts by mass, and further preferably 0.8 to 1.5 parts by mass. By making the content of the crystallization nucleating agent (C) 0.6 parts by mass or more, the temperature conditions for crystallization can be widely set, and productivity can be improved. In addition, by making it 2.0 parts by mass or less, the amount of gas components generated during molding can be suppressed, and a good appearance can be obtained.
[0258] As the crystal nucleating agent (C), the same crystal nucleating agent as the crystal nucleating agent (C) exemplified in the first embodiment of the present invention is preferred. Among them, from the viewpoint of increasing the crystallization temperature, it is preferred to use a lithium salt of an organic compound of phosphoric acid or phosphorous acid, and more preferably to use lithium [phosphate [2,2'-methylenebis (4,6-di-tert-butylphenyl)] ester].
[0259] <Modified polyphenylene ether (D)>
[0260] In the resin-metal composite of the second aspect of the present invention, the thermoplastic resin composition (T2) preferably further contains a modified polyphenylene ether (D). When the thermoplastic resin composition (T2) contains the modified polyphenylene ether (D), the interface strength between the thermoplastic resin composition (T2) and the glass filler (G) described below can be improved, so that the strength of the structure as the resin part is increased, and the thermal shock resistance of the resin-metal composite can be improved.
[0261] In addition, in the thermoplastic resin composition (T2), the content of the modified polyphenylene ether (D) is preferably 0.1 to 15.0 parts by mass, more preferably 0.1 to 10.0 parts by mass, and further preferably 0.1 to 6.0 parts by mass, relative to 100 parts by mass of the styrene resin composition (S2). By making the content of the modified polyphenylene ether (D) 0.1 parts by mass or more, the interfacial strength between the thermoplastic resin composition (T2) and the glass filler (G) described later can be improved, so that the strength of the structure as the resin part becomes higher, and the heat shock resistance of the resin-metal composite can be improved. In addition, by being 15 parts by mass or less, sufficient crystallinity can be ensured, and heat resistance and rigidity can be easily ensured.
[0262] The modified polyphenylene ether (D) used in the resin-metal composite of the second aspect of the present invention has compatibility with SPS (A) and improves compatibility with other components, and preferably has a polar group that can react with the glass filler (G2).
[0263] Thus, the modified polyphenylene ether (D) is blended for the purpose of improving the compatibility of SPS (A) with other components, especially the glass filler (G2), and improving the interface strength between the components. More specifically, the modified polyphenylene ether (D) is preferably an acid-modified polyphenylene ether.
[0264] The polar group reactive with the glass filler (G2) is a functional group reactive with the polar group of the glass filler (G2), and specific examples thereof are preferably the same functional groups as those exemplified in the first embodiment of the present invention, and more preferably a carboxylic acid group.
[0265] As the modified polyphenylene ether (D), fumaric acid-modified polyphenylene ether and maleic anhydride-modified polyphenylene ether are preferred, and fumaric acid-modified polyphenylene ether is more preferred.
[0266] The modification amount (modifier content) of the modified polyphenylene ether (D) is preferably 0.1 to 20% by mass, more preferably 0.2 to 15% by mass, further preferably 0.3 to 10% by mass, and further preferably 0.5 to 5.0% by mass. By setting the modification amount within the above range, the interfacial strength between the thermoplastic resin composition (T2) and the glass filler (G2) described below can be increased, thereby increasing the strength of the structure as the resin portion.
[0267] Preferred examples of the polyphenylene ether are the same polyphenylene ethers as those exemplified in the first aspect of the present invention.
[0268] In addition, as the modifier used in the modification of the polyphenylene ether, there can be mentioned compounds having an olefinic double bond and a polar group in the same molecule, specifically, there can be mentioned the same modifiers as those exemplified in the first embodiment of the present invention, and maleic anhydride, fumaric acid and glycidyl methacrylate are particularly preferably used, and fumaric acid is more preferably used. The above-mentioned various modifiers can be used alone or in combination of two or more.
[0269] The modified polyphenylene ether (D) is obtained by reacting the polyphenylene ether with a modifier. The modification method is not particularly limited, and the same modification method as exemplified in the first embodiment of the present invention can be mentioned. Preferably, melt modification and solution modification can be mentioned, and melt modification is more preferred. That is, the modified polyphenylene ether (D) is preferably a modified polyphenylene ether produced by melt modification or a modified polyphenylene ether produced by solution modification, and more preferably a modified polyphenylene ether produced by melt modification.
[0270] In addition, specific various conditions for melt modification are preferably the same various conditions as those exemplified for the melt modification in the first aspect of the present invention.
[0271] <Antioxidant (E)>
[0272] From the viewpoint of heat resistance, the thermoplastic resin composition (T2) preferably further contains an antioxidant (E). The antioxidant (E) is preferably one or more selected from phenolic compounds, phosphorus compounds and sulfur compounds, and from the viewpoint of heat resistance, phenolic compounds are more preferred.
[0273] Specific examples of the phenolic antioxidant include the same phenolic antioxidants as exemplified in the first embodiment of the present invention, and pentaerythritol tetrakis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate} is particularly preferred.
[0274] Examples of the phosphorus-based antioxidant include monophosphites such as tris(2,4-di-tert-butylphenyl) phosphite and tris(mononyl- and dinonylphenyl) phosphite, and bisphosphites.
[0275] Examples of the sulfur-based antioxidant include 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-(dodecylthio)propionate], ditridecyl 3,3'-thiodipropionate, and 3,3'-thiodipropionate.
[0276] In the thermoplastic resin composition (T2), the content of the antioxidant (E) is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.15 parts by mass or more, relative to 100 parts by mass of the styrene resin composition (S2). In addition, it is preferably 2.0 parts by mass or less, more preferably 1.0 parts by mass or less, and further preferably 0.7 parts by mass or less. If the amount of the antioxidant is within the above range, heat discoloration resistance during processing becomes good, and long-term heat resistance can be obtained, and the oozing of the antioxidant can be suppressed, and the appearance will not be adversely affected.
[0277] <Release agent (F)>
[0278] The thermoplastic resin composition (T2) preferably further contains a release agent (F).
[0279] As the release agent (F), any one selected from known release agents such as polyethylene wax, silicone oil, and long-chain carboxylic acid can be used.
[0280] In the thermoplastic resin composition (T2), the content of the release agent (F) is preferably 0.05 to 3.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, further preferably 0.1 to 1.5 parts by mass, and further preferably 0.1 to 1.0 parts by mass, based on 100 parts by mass of the styrene resin composition (S2).
[0281] <Glass filler (G2)>
[0282] In the second aspect of the present invention, the reinforced thermoplastic resin composition contains a glass filler (G2), thereby reducing the CTE. TD , reduce CTE TD -CTE M , which can improve the thermal shock resistance of the resin-metal composite.
[0283] In the present invention, the glass filler (G2) is preferably one or more selected from glass fibers and glass flakes having a flat cross section. By using the glass filler (G2) as one or more selected from glass fibers and glass flakes having a flat cross section, the linear expansion coefficient of the resin member can be easily reduced. In particular, by using the glass filler (G2) selected from the above, not only the linear expansion coefficient of MD but also the linear expansion coefficient of TD (CTE TD ), thus reducing CTE TD -CTE M , since it can improve the thermal shock resistance of the resin-metal composite, it is preferred.
[0284] (Glass fiber with a flat cross section)
[0285] In a glass fiber having a flat cross section, the flat shape refers to a shape in which the profile ratio of the glass fiber is greater than 1. In the present invention, the profile ratio refers to the ratio of the major diameter to the minor diameter of the cross section perpendicular to the fiber axis of the glass fiber having a flat cross section, i.e., the major diameter / minor diameter. In addition, the major diameter refers to the straight line distance of the longest portion between two points on the outer edge of the cross section passing through the center of gravity in the cross section perpendicular to the fiber axis, and the minor diameter refers to the straight line distance between two points intersecting the outer edge of the cross section passing through the center of gravity.
[0286] By using glass fibers with a flat cross-section, the CTE can be reduced. TD , thus reducing CTE TD -CTE M , which can improve the thermal shock resistance of the resin-metal composite.
[0287] From reducing CTE TD -CTE M From the viewpoint of improving the heat shock resistance of the resin-metal composite, the profile ratio of the glass fiber having a flat cross section is preferably 2.0 to 6.0, more preferably 3.0 to 5.0, and further preferably 3.5 to 4.5. In addition, the minor diameter is preferably 3 μm to 10 μm, and more preferably 5 μm to 8 μm.
[0288] The major axis and minor axis of the glass fiber are both number averages, which are measured by performing image analysis on 50 or more arbitrarily selected glass fibers using a digital microscope and calculated as the number average.
[0289] From reducing CTE TD -CTE M From the viewpoint of improving the heat shock resistance of the resin-metal composite, the fiber diameter of the glass fiber having a flat cross section is preferably 10 μm or more, more preferably 10.5 μm or more, further preferably 11 μm or more, and further preferably 12 μm or more. In addition, from the viewpoint of ensuring the fluidity of the reinforced thermoplastic resin composition during molding, the fiber diameter of the glass fiber having a flat cross section is preferably 20 μm or less, and more preferably 18 μm or less.
[0290] It should be noted that, in the present invention, the fiber diameter of the glass fiber with a flat cross-section refers to the diameter of a circle obtained by converting a cross-section perpendicular to the fiber axis into a circle with an area equal to the area of the cross-section. The fiber diameter of the glass fiber is a number average, and is measured and calculated by performing image analysis using a digital microscope to arbitrarily selected glass fibers of more than 50.
[0291] From the viewpoint of ensuring the fluidity and handleability of the reinforced thermoplastic resin composition during molding, the fiber length of the glass fiber having a flat cross section is preferably 1 to 50 mm, more preferably 1.5 to 15 mm, and further preferably 2 to 8 mm. In addition, the fiber length of the glass fiber having a flat cross section is preferably included in the resin composition pellets in a state of 300 to 600 μm due to breakage during extrusion kneading.
[0292] The fiber length of the glass fibers is a number average, and is measured and calculated by performing image analysis on 50 or more arbitrarily selected glass fibers using a digital microscope.
[0293] (glass sheet)
[0294] The glass flakes are preferably flaky particles. The flaky particles are flat particles having an average thickness smaller than an average minor diameter.
[0295] By using glass sheets, the CTE can be reduced TD , thus reducing CTE TD -CTE M , which can improve the thermal shock resistance of the resin-metal composite.
[0296] From reducing CTE TD -CTE M From the viewpoint of improving the thermal shock resistance of the resin-metal composite, the aspect ratio of the average major axis to the average minor axis of the glass flakes (average major axis / average minor axis) is preferably 3.0 or less, more preferably 2.0 or less, and even more preferably 1.6 or less.
[0297] In addition, reducing CTE TD -CTE M From the viewpoint of improving the thermal shock resistance of the resin-metal composite, the aspect ratio of the average major axis to the average thickness of the glass flakes (average major axis / average thickness) is preferably 5 or more, more preferably 10 or more, and even more preferably 30 or more.
[0298] From the viewpoint of ensuring the fluidity and handleability of the reinforced thermoplastic resin composition during molding, the average major diameter of the glass flakes is preferably 1000 μm or less, more preferably 1 to 500 μm, and further preferably 1 to 200 μm. In addition, from the viewpoint of ensuring the fluidity and handleability of the reinforced thermoplastic resin composition during molding, the average minor diameter of the glass flakes is preferably 1000 μm or less, more preferably 1 to 500 μm, and further preferably 1 to 200 μm.
[0299] The average major axis, average minor axis and average thickness of the glass flakes are all number averages, and are measured and calculated by performing image analysis on 50 or more arbitrarily selected glass flakes using a digital microscope.
[0300] In order to improve the adhesion with SPS (A), the glass filler (G2) is preferably surface-treated with a coupling agent, more preferably treated with a silane coupling agent or a titanium coupling agent, and further preferably treated with a silane coupling agent from the viewpoint of compatibility with the resin component.
[0301] Specific examples of the silane coupling agent include the same silane coupling agents as those exemplified in the first embodiment of the present invention, preferably aminosilanes and epoxysilanes such as γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0302] Specific examples of the titanium coupling agent include the same titanium coupling agents as those exemplified in the first embodiment of the present invention, and tris(N-amidoethyl, aminoethyl)titanate isopropyl is preferred.
[0303] The content of the glass filler (G2) in the reinforced thermoplastic resin composition in the second embodiment of the present invention is preferably 20.0 to 65.0% by mass, more preferably 23.0 to 55.0% by mass, and even more preferably 25.0 to 45.0% by mass, in the total of 100% by mass of the thermoplastic resin composition (T2) and the glass filler (G2). By setting the content of the glass filler (G2) to 20.0% by mass or more, the CTE can be reduced. TD , reduce CTE TD -CTE M , the thermal shock resistance of the resin-metal composite can be improved. By setting the content of the glass filler (G2) to 65.0 mass % or less, the fluidity of the reinforced thermoplastic resin composition during molding can be ensured.
[0304] <Other ingredients>
[0305] To the reinforced thermoplastic resin composition in the second aspect of the present invention, other optional components may be added within a range that does not hinder the purpose of the present invention.
[0306] As other components, a colorant, a crosslinking agent, a crosslinking auxiliary agent, a dispersant, a plasticizer, an antifouling agent, an ultraviolet absorber, a light stabilizer, a flame retardant, a flame retardant auxiliary agent, an antistatic agent, and the like may be contained as optional components.
[0307] Specific examples of the colorant, dispersant, ultraviolet absorber, light stabilizer, flame retardant and flame retardant aid include the same colorants, dispersants, ultraviolet absorbers, light stabilizers, flame retardants and flame retardant aids as exemplified in the first embodiment of the present invention.
[0308] (Manufacture of reinforced thermoplastic resin composition)
[0309] In the resin-metal composite of the second embodiment of the present invention, the reinforced thermoplastic resin composition is obtained by blending and kneading a styrene resin (A) having a syndiotactic structure, a rubbery elastomer (B) and a glass filler (G2), and, if necessary, the above-mentioned crystal nucleating agent (C), a modified polyphenylene ether (D), an antioxidant (E), a release agent (F) and other components to obtain a composition.
[0310] The compounding and kneading can be carried out by premixing using commonly used equipment such as a ribbon mixer, a tumbler, a Henschel mixer, etc., using a Banbury mixer, a single-screw extruder, a twin-screw extruder, a multi-screw extruder, a co-kneader, etc.
[0311] <Metal components>
[0312] The metal member of the resin-metal composite of the second embodiment of the present invention is preferably at least one selected from aluminum, stainless steel, copper, titanium and alloys thereof, and more preferably at least one selected from aluminum, stainless steel and copper. These metals can be selected according to the intended use and physical properties, and copper or copper alloys are more preferably used. The shape of the metal member is not particularly limited, and for example, it can be a flat plate, a curved plate, a rod, a cylinder, a block, etc. It can also be a structure composed of a combination of them.
[0313] <Application>
[0314] The resin-metal composite of the second embodiment of the present invention is not prone to damage such as cracks even when alternately exposed to a high temperature environment and a low temperature environment, and has excellent durability and so-called heat shock resistance. Therefore, for example, in the electronic / electromechanical field, the automotive field, and the home appliance field, as a component formed by integrating metal and resin as different materials, it can be used in a harsh environment such as alternately exposed to a high temperature environment and a low temperature environment. As for the use temperature range, for example, it can be used in a temperature range of 110°C or more and 150°C or less as a high temperature environment and -50°C or more and -30°C or less as a low temperature environment, and can also be used in an environment where the temperature difference changes from 140°C or more to 160°C or more. Specifically, the resin-metal composite of the second embodiment of the present invention can be used as a terminal block and busbar member used in control circuit wiring for lithium-ion batteries and electric vehicles mounted on vehicles, a terminal block and busbar member used in a panel such as a switchboard, a distribution panel, and a control panel, a terminal block and busbar member used in a relay box of electric wires used in large machinery, and an electromagnetic valve.
[0315] Example
[0316] The present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0317] The raw materials used in Examples and Comparative Examples are as follows.
[0318] <SPS (Syndiotactic polystyrene) (A)>
[0319] ・SPS-30: Syndiotactic polystyrene resin, weight average molecular weight: 150,000, MFR: 30 g / 10 min, manufactured by Idemitsu Kosan Co., Ltd.
[0320] ・SPS-13: Syndiotactic polystyrene resin, weight average molecular weight: 180,000, MFR: 13 g / 10 min, manufactured by Idemitsu Kosan Co., Ltd.
[0321] ・SPS-09: Syndiotactic polystyrene resin, weight average molecular weight: 200,000, MFR: 9 g / 10 min, manufactured by Idemitsu Kosan Co., Ltd.
[0322] ・SPS-06: Syndiotactic polystyrene resin, weight average molecular weight: 230,000 to 250,000, MFR: 6 g / 10 minutes, manufactured by Idemitsu Kosan Co., Ltd.
[0323] <Rubber-like elastic body (B)>
[0324] ・SEPTON8006: SEPTON8006, hydrogenated styrene-butadiene-styrene block copolymer, styrene content 33%, manufactured by Kuraray Co., Ltd.
[0325] <Crystallization nucleating agent (C)>
[0326] ・NA-70: ADKSTAB NA-70, lithium phosphate (2,2'-methylenebis(4,6-di-tert-butylphenyl)), manufactured by ADEKA Corporation
[0327] ・NA-11: ADKSTAB NA-11, sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, manufactured by ADEKA Co., Ltd.
[0328] <Modified polyphenylene ether (D)>
[0329] ・Fumaric acid-modified polyphenylene ether, manufactured by Idemitsu Kosan Co., Ltd., modification amount 1.5 mass%
[0330] <Antioxidant (E)>
[0331] ・Antioxidant, Irganox 1010: Irganox 1010, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by BASF Corporation
[0332] <Release agent (F)>
[0333] ・KF-53: Methylphenyl silicone oil, manufactured by Shin-Etsu Silicone Co., Ltd.
[0334] <Glass fiber (G) having a flat cross section (glass filler (G2))>
[0335] ・3PA-820: CSG 3PA-820, cross section: flat shape (minor diameter: 7μm, profile ratio: 4), fiber length: 3mm, manufactured by Nitto Bosho Co., Ltd.
[0336] ・3J-820: CSG 3J-820, cross section: flat shape, fiber diameter: 10.5μm (minor diameter: 5μm, profile ratio: 4), fiber length: 3mm, manufactured by Nitto Bosho Co., Ltd.
[0337] ・T-249-FGF: ECS 03 T-249-FGF, cross section: flat shape (minor diameter: 7μm, profile ratio: 4), fiber length: 3mm, manufactured by Nippon Electric Glass Co., Ltd.
[0338] <Glass fiber not having a flat cross section>
[0339] ・T-249H: ECS 03 T-249H, cross section: perfect circle, fiber diameter: 10.5μm, fiber length: 3mm, manufactured by Nippon Electric Glass Co., Ltd.
[0340] <Glass flakes (glass filler (G2))>
[0341] ・REFG315: Fleka REFG-315, average major diameter: 160μm, average minor diameter: 160μm, average thickness: 5μm, aspect ratio (average major diameter / average minor diameter): 1, aspect ratio (average major diameter / average thickness): 32, manufactured by Nippon Sheet Glass Co., Ltd.
[0342] [Examples of the fiber-reinforced thermoplastic resin composition according to the first aspect of the present invention]
[0343] Examples 1-1 to 1-14, Comparative Examples 1-1 to 1-11
[0344] (Manufacture of fiber-reinforced thermoplastic resin composition)
[0345] Each component other than the glass fiber (G) was mixed in the ratios listed in Tables 1 and 2 and dry-blended using a Henschel mixer. Next, a twin-screw extruder TEM37SS (manufactured by Shibaura Machine Co., Ltd.) was used to knead the resin composition while side-feeding the glass fiber (G) in the ratios listed in Tables 1 and 2 at a screw speed of 220 rpm and a barrel temperature of 270 to 290°C to produce pellets. The obtained pellets were dried at 120°C for 5 hours using a hot air dryer to obtain pellets of a fiber-reinforced thermoplastic resin composition. The obtained pellets of the fiber-reinforced thermoplastic resin composition were used for evaluation.
[0346] (1) SFL (Spiral Flow Length)
[0347] The SFL (unit: mm) of the obtained fiber-reinforced thermoplastic resin composition was measured using an injection molding machine MD100Xi2.7 (manufactured by Nigata Machine Techno Co., Ltd.). The injection conditions during the measurement were set to a barrel temperature of 290°C, a mold temperature of 150°C, and an injection pressure of 100 MPa. A spiral flow mold with a flow path thickness of 1 mm, a width of 10 mm, and an Archimedean spiral shape was used. The larger the SFL value, the better the fluidity. The results are shown in Tables 1 and 2.
[0348] (2) Tensile test
[0349] Using an injection molding machine SH100A (manufactured by Sumitomo Heavy Industries, Ltd.), a dumbbell-shaped test piece with a thickness of 4 mm formed from the pellets of the obtained fiber-reinforced thermoplastic resin composition was made at a resin temperature of 290°C and a mold surface temperature of 150°C. Here, as a dumbbell-shaped test piece, a multi-purpose test piece (type A1) according to JIS K7139:2009 was made. Using the obtained dumbbell-shaped test piece, the tensile fracture stress and tensile fracture strain were measured according to ISO 527-1,2:2019. The higher the tensile fracture stress and tensile fracture strain, the better the toughness. The results are shown in Tables 1 and 2.
[0350] (3) Reflow heat resistance
[0351] A square plate test piece of 80 mm×80 mm×2 mm thick was prepared from the obtained fiber-reinforced thermoplastic resin composition pellets using an injection molding machine MD100Xi2.7 (manufactured by Nigata Machine Techno Co., Ltd.) at a resin temperature of 290°C and a mold surface temperature of 150°C.
[0352] The solder heat resistance of the square plate test piece was determined using a reflow oven UNI-5016F (manufactured by ANTOM Co., Ltd., Japan) by the reflow method according to IEC60068-2-58 (2015, 4th edition). In the reflow temperature curve of the reflow method, the time exceeding the peak temperature of 260°C and 255°C was set to 25 seconds, and the reflow process was performed.
[0353] The dimensional changes in the resin flow direction (MD) and the direction perpendicular to the resin flow direction (TD) of the test piece before and after the reflow treatment were measured to obtain the reflow treatment shrinkage rate of MD and the reflow treatment shrinkage rate of TD. In addition, based on the reflow treatment shrinkage rate of MD and the reflow treatment shrinkage rate of TD, the anisotropy of the reflow treatment shrinkage rate (TD / MD) was obtained according to the following formula. The smaller the reflow treatment shrinkage rate in each direction and the closer the value of the anisotropy of the reflow treatment shrinkage rate is to 1, the better the reflow heat resistance is. The results are shown in Tables 1 and 2. It should be noted that the values of the anisotropy of the reflow treatment shrinkage rate (TD / MD) in Tables 1 and 2 are values calculated based on the values of the reflow treatment shrinkage rate of MD and the reflow treatment shrinkage rate of TD before rounding the values.
[0354] (Anisotropy of reflow shrinkage) = (Reflow shrinkage in TD / Reflow shrinkage in MD)
[0355] (4) Load deflection temperature
[0356] Using an injection molding machine SH100A (manufactured by Sumitomo Heavy Industries, Ltd.), at a resin temperature of 290°C and a mold surface temperature of 150°C, a long test piece of 80 mm×10 mm×4 mm in thickness was prepared from the obtained fiber-reinforced thermoplastic resin composition.
[0357] The obtained long test piece was used to measure the deflection temperature under load (load 1.8 MPa) in accordance with ISO75-1,2:2020. The higher the deflection temperature under load, the better the heat resistance. The results are shown in Tables 1 and 2.
[0358] (5) Crystallization temperature
[0359] The crystallization temperature was measured using a differential scanning calorimeter DSC8500 (manufactured by PerkinElmer, Inc.). The pellets of the obtained fiber-reinforced thermoplastic resin composition were sealed in an aluminum pan, heated from room temperature to 300°C at a rate of 20°C / min under a nitrogen atmosphere, maintained at 300°C for 1 minute, and then cooled to room temperature at a rate of 20°C / min. The temperature of the peak top in the measured crystallization peak was taken as the crystallization temperature. The higher the crystallization temperature, the more widely the temperature conditions for crystallization can be set, and the productivity can be improved. The results are shown in Tables 1 and 2.
[0360] Tables 1 and 2 show the evaluation results of the fiber-reinforced thermoplastic resin compositions.
[0361] [Table 1]
[0362]
[0363] [Table 2]
[0364]
[0365] The results in Tables 1 and 2 show that the fiber-reinforced thermoplastic resin composition of the first embodiment of the present invention has excellent heat resistance and dimensional stability at high temperatures. Therefore, the fiber-reinforced thermoplastic resin composition of the present invention is particularly suitable for use as a reflow-resistant resin material.
[0366] [Examples of the resin-metal composite according to the second aspect of the present invention]
[0367] Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-10
[0368] Each component other than the glass filler (G2) was mixed in the ratios listed in Tables 3 and 4 and dry-blended using a Henschel mixer. Next, a twin-screw extruder TEM37SS (manufactured by Shibaura Machine Co., Ltd.) was used to knead the resin composition while side-feeding the glass filler (G2) in the ratios listed in Tables 3 and 4 at a screw speed of 250 rpm and a barrel temperature of 290°C to produce pellets. The obtained pellets were dried at 120°C for 5 hours using a hot air dryer to obtain pellets of a reinforced thermoplastic resin composition. The obtained pellets of the reinforced thermoplastic resin composition were used for evaluation.
[0369] (1) Linear expansion coefficient
[0370] (1-1) TD linear expansion coefficient (CTE) of the resin component TD )
[0371] Using an injection molding machine SE100-EV (manufactured by Sumitomo Heavy Industries, Ltd.), a dumbbell-shaped test piece with a thickness of 4 mm was prepared from the pellets of the obtained reinforced thermoplastic resin composition at a barrel temperature of 290°C and a mold temperature of 150°C. Here, as the dumbbell-shaped test piece, a multi-purpose test piece (type A1) in accordance with JIS K7139:2009 was prepared. From the obtained dumbbell-shaped tensile test piece, Figure 4 The linear expansion coefficient (CTE) of TD TD ) The test piece is cut out at the position of the cutout portion 32 of the test piece for measurement. The size of the test piece is set to 4 mm×4 mm×10 mm.
[0372] The obtained test piece was used to measure the coefficient of linear expansion (CTE) of the resin member in TD using a thermomechanical analyzer (TMA7100 manufactured by Hitachi High-Tech Co., Ltd.) under the following measurement conditions: TD ).
[0373] ≪Measurement conditions≫
[0374] ・Testing equipment: Thermomechanical analyzer (TMA7100, manufactured by Hitachi High-Tech Co., Ltd.)
[0375] ・Measurement mode: Compression
[0376] ・Measurement temperature: -60~270℃
[0377] ・Heating temperature: 5℃ / min
[0378] ・Evaluation area: -40~120℃
[0379] (1-2) Coefficient of linear expansion (CTE) of metal components M )
[0380] The coefficient of linear expansion (CTE) of metal components M ) was measured in accordance with JIS Z2285: 2003. It should be noted that the linear expansion coefficient (CTE) of the metal member (made of stainless steel (SUS304)) used in the examples is M ) is 1.73×10 -5 / ℃.
[0381] (2) Bending fracture strain of parallel flow welded test pieces formed from reinforced thermoplastic resin compositions
[0382] (Preparation of test pieces)
[0383] Using the injection molding machine SE100-EV (manufactured by Sumitomo Heavy Industries, Ltd.), Figure 2 and 3 The mold of the shape shown was made at a barrel temperature of 290°C and a mold temperature of 150°C. Figure 1 The thickness of the measurement molded body 1 is 2 mm.
[0384] like Figure 1 As shown, from the obtained test molded body, a parallel flow welded bending fracture strain measurement test piece with a width of 10 mm, a length of 80 mm, and a thickness of 2 mm was cut out at a position 50 to 60 mm away from the gate portion 13A of flow path A and the gate portion 13B of flow path B on MD.
[0385] The obtained parallel flow welded bending fracture strain measurement test piece was used to perform a bending test under the following measurement conditions in accordance with ISO178:2010 to measure the bending fracture strain of the parallel flow welded test piece formed from the reinforced thermoplastic resin composition. Figure 1 The parallel flow welding portion 12 is set in a manner that the pressure head is pressed.
[0386] ≪Measurement conditions≫
[0387] ・The distance between the pivot points is 30mm
[0388] ・Fulcrum radius is 2mm
[0389] ・Indenter radius is 5mm
[0390] ・Test speed is 1mm / min
[0391] (3) Thermal shock resistance
[0392] An injection molding machine SE50-EV (manufactured by Sumitomo Heavy Industries, Ltd.) was used. Figure 7As shown in FIG. 1 , a metal member (stainless steel (SUS304), size: 6 mm × 6 mm × 103 mm) was set in the cavity of the mold, and a test piece for heat shock resistance evaluation was prepared at a barrel temperature of 290°C and a mold temperature of 150°C. In the test piece for heat shock resistance evaluation, Figure 5 As shown in FIG. 1 , the resin member is covered on the metal member in a shape of a radius of 10 mm and a length of 85 mm. Figure 6 In the cross section shown, the minimum wall thickness of the resin member is 0.76 mm. In the resin member of the test piece for evaluating thermal shock resistance, a weld line exists in the longitudinal direction on the side opposite to the gate portion.
[0393] The obtained test pieces for evaluating thermal shock resistance were used to perform a thermal shock test using a small thermal shock apparatus TES-12-A (manufactured by ESPEC Co., Ltd.) under the following measurement conditions. The minimum value of the number of cycles at which cracks occurred at the weld line was measured among the three test pieces for evaluating thermal shock resistance, and the thermal shock resistance was evaluated based on the following evaluation criteria.
[0394] ≪Measurement conditions≫
[0395] ・One cycle conditions: -40°C for 45 minutes → 120°C for 45 minutes
[0396] ≪Evaluation Criteria≫
[0397] A: The minimum number of cycles for cracking is greater than 250 cycles.
[0398] B: The minimum value of the number of cycles at which cracks occurred was more than 200 cycles and not more than 250 cycles.
[0399] C: The minimum value of the number of cycles at which cracks occurred was more than 100 cycles and not more than 200 cycles.
[0400] D: The minimum number of cycles to produce cracks is less than 100 cycles
[0401] Tables 3 and 4 show the evaluation results of the resin-metal composites.
[0402] [Table 3]
[0403]
[0404] [Table 4]
[0405]
[0406] From the results in Table 3 and Table 4, it can be seen that the resin-metal composite according to the second embodiment of the present invention has excellent thermal shock resistance.
[0407] Description of Reference Numerals
[0408] 1: Formed body for measuring bending fracture strain of parallel flow welding
[0409] 11: Cut-out portion of test piece
[0410] 12: Parallel welding section
[0411] 13A: Gate of flow path A
[0412] 13B: Gate of flow path B
[0413] 2: Mold for forming a molded body for measuring bending fracture strain of parallel flow welding
[0414] 21: Upper part of mold
[0415] 22: Lower part of the mold
[0416] 23: Chamber
[0417] 24: Resin inlet
[0418] 25: Next door
[0419] 26: Resin confluence
[0420] 31: Dumbbell-shaped test piece
[0421] 32: TD linear expansion coefficient (CTE TD ) Cut-out portion of the test piece for measurement
[0422] 4: Test piece for evaluation of thermal shock resistance
[0423] 41: Resin components
[0424] 42: Metal components
[0425] 43: Gate
[0426] 44: Location of weld line
[0427] 5: Mold for test piece for thermal shock resistance evaluation
[0428] 51: Chamber
[0429] 52: Resin inlet
Claims
1. A fiber-reinforced thermoplastic resin composition comprising a thermoplastic resin composition (T) and a glass fiber (G) having a flat cross section, The thermoplastic resin composition (T) comprises 100 parts by mass of a styrene resin composition (S) and 0.6 to 2.0 parts by mass of a crystal nucleating agent (C), wherein the styrene resin composition (S) is composed of 83 to 100 parts by mass of a styrene polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 0 to 17 parts by mass of a rubbery elastomer (B). The content of the glass fiber (G) is 33.0% by mass to 65.0% by mass based on the total of the thermoplastic resin composition (T) and the glass fiber (G).
2. The fiber-reinforced thermoplastic resin composition according to claim 1, wherein The modified polyphenylene ether (D) is further contained in an amount of 0.1 to 5.0 parts by mass based on 100 parts by mass of the styrene resin composition (S).
3. The fiber-reinforced thermoplastic resin composition according to claim 1 or 2, wherein: The weight average molecular weight of the styrene-based polymer (A) is less than 200,000.
4. The fiber-reinforced thermoplastic resin composition according to any one of claims 1 to 3, wherein The profile ratio of the glass fiber (G) is 3.5 to 4.
5.
5. The fiber-reinforced thermoplastic resin composition according to any one of claims 1 to 4, wherein The glass fiber (G) has a fiber diameter of 10 μm or more.
6. The fiber-reinforced thermoplastic resin composition according to any one of claims 1 to 5, wherein The reflow shrinkage TD measured by treating a test piece formed of the fiber-reinforced thermoplastic resin composition in accordance with IEC60068-2-58 is 0.20% or less, and the anisotropy TD / MD of the reflow shrinkage is 4.5 or less.
7. The fiber-reinforced thermoplastic resin composition according to any one of claims 1 to 6, wherein The test piece formed of the fiber-reinforced thermoplastic resin composition has a deflection temperature under load measured in accordance with Method A of ISO 75-1,2 (2020) of 255° C. or higher. 8 . A reflow-resistant resin material comprising the fiber-reinforced thermoplastic resin composition according to claim 1 . 9 . A molded body for reflow soldering, comprising the reflow soldering resistant resin material according to claim 8 . 10 . A resin-metal composite comprising the molded article for reflow soldering according to claim 9 and a metal member.
11. A connector formed of the resin-metal composite according to claim 10.
12. The connector according to claim 11, which is used in a reflow soldering process.
13. The connector according to claim 11, which is used in a reflow soldering process based on surface mounting.
14. A resin-metal composite comprising: A resin member formed of a reinforced thermoplastic resin composition containing a thermoplastic resin composition (T2) and a glass filler (G2); and Metal components, The linear expansion coefficient CTE of the TD of the resin member TD The linear expansion coefficient CTE of the metal component M CTE TD -CTE M 6.0×10 -5 / ℃ below, A parallel flow welded test piece formed from the reinforced thermoplastic resin composition has a bending fracture strain of 1.15% or more.
15. The resin-metal composite according to claim 14, wherein The thermoplastic resin composition (T2) comprises a styrene resin composition (S2), wherein the styrene resin composition (S2) comprises 75 to 94 parts by mass of a styrene polymer (A) having a syndiotactic structure and a weight average molecular weight of less than 230,000 and 6 to 25 parts by mass of a rubbery elastomer (B).
16. The resin-metal composite according to claim 14 or 15, wherein The glass filler (G2) is one or more selected from glass fibers and glass flakes having a flat cross section.
17. The resin-metal composite according to claim 16, wherein The glass fiber having a flat cross section has a profile ratio of 3.5 to 4.
5.
18. The resin-metal composite according to claim 16 or 17, wherein The glass fiber having a flat cross section has a fiber diameter of 10 μm or more.
19. The resin-metal composite according to any one of claims 16 to 18, wherein The glass flakes are flaky particles.
20. The resin-metal composite according to any one of claims 14 to 19, wherein The content of the glass filler (G2) is 20.0% by mass to 65.0% by mass based on the total of the thermoplastic resin composition (T2) and the glass filler (G2).
21. The resin-metal composite according to any one of claims 15 to 20, wherein The thermoplastic resin composition (T2) further contains 0.6 to 2.0 parts by mass of a crystal nucleating agent (C) based on 100 parts by mass of the styrene resin composition (S2).
22. The resin-metal composite according to any one of claims 15 to 21, wherein The thermoplastic resin composition (T2) further contains 0.1 to 15.0 parts by mass of a modified polyphenylene ether (D) based on 100 parts by mass of the styrene resin composition (S2).
23. The resin-metal composite according to any one of claims 15 to 22, wherein The thermoplastic resin composition (T2) further contains 0.05 to 3.0 parts by mass of a release agent (F) based on 100 parts by mass of the styrene resin composition (S2).
24. The resin-metal composite according to any one of claims 15 to 23, wherein The weight average molecular weight of the styrene-based polymer (A) is less than 200,000.
25. The resin-metal composite according to any one of claims 14 to 24, wherein The metal member is at least one selected from the group consisting of aluminum, stainless steel, copper, titanium, and alloys thereof.
Citation Information
Patent Citations
Thermoplastic resin composition and molded product thereof
JP2004155928A
Insert molded product
JP2005161693A
Styrene-based polymer and its molded article
JP2009068022A
Polyarylene sulfide-based resin composition and insert molding
JP2020109135A
Styrene resin, styrene resin composition, molded article thereof, and styrene resin production method
WO2019107526A1